Modified current collector for secondary battery
By using modified set flows in lithium -ion battery electrodes, the stream corrosion and interface resistance problems caused by water -based slurry are solved, and better electrochemical properties and stability are achieved.
Patent Information
- Application Number
- CN202280096543.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-31
- Publication Date
- 2025-01-28
AI Technical Summary
When using water-based slurry for existing lithium-ion battery electrodes, the reaction of the electrode active material with water causes corrosion of the current collector, and the interface resistance between the electrode layer and the current collector is high, affecting the electrochemical performance of the battery.
The modified set is used, which contains a conductive layer on the base and the on -base side or on both sides. The conductive layer consists of conductive material and adhesive material. Prevent base corrosion.
The conductive layer of the modified set is used as a physical barrier to prevent the base corrosion and reduce the interface resistance between the electrode layer and the streaming.
Smart Images

Figure CN119384739A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries. In particular, the present invention relates to modified current collectors for battery electrodes in secondary batteries. Background Art
[0002] Among various types of batteries, lithium-ion batteries (LIBs) have been widely used in various applications over the past decades, especially in consumer electronics, due to their excellent energy density, long cycle life, and high discharge capacity. Due to the rapid market development of electric vehicles (EVs) and grid energy storage, high-performance, low-cost LIBs currently provide one of the most promising options for large-scale energy storage devices. However, in the current lithium-ion battery technology, more specifically, in the technology of lithium-ion battery electrodes, many problems still exist.
[0003] Typically, lithium-ion battery electrodes are manufactured by casting an organic-based slurry on a current collector. The slurry contains an electrode active material, conductive carbon, and a binder in an organic solvent. The binder provides good electrochemical stability, fixing the electrode active materials together and adhering them to the current collector during electrode preparation. Polyvinylidene fluoride (PVDF) is one of the most commonly used binders in the current commercial lithium-ion battery industry. However, PVDF is insoluble in water and can only be dissolved in some specific organic solvents, such as N-methyl-2-pyrrolidone (NMP), which is flammable and toxic, and therefore requires special handling.
[0004] During the drying process, an NMP recovery system must be installed to recover the NMP vapor. This will incur high costs in the manufacturing process because it requires a large amount of capital investment. In view of the shortcomings of organic-based slurries, the present invention preferably uses water-based slurries, which use cheaper and environmentally friendly solvents, such as aqueous solvents, most commonly water. These aqueous solvents are significantly safer and easier to handle than NMP, and do not require the implementation of a recovery system.
[0005] However, there are problems with using water-based slurries in the manufacture of lithium-ion batteries. Specifically, the electrode active materials may react with water and have undesirable effects on the current collector. This problem is particularly evident when using nickel-containing cathode active materials such as lithium nickel manganese cobalt oxide (NMC) because they react strongly with water and form alkaline solutions. Therefore, when the nickel-containing water-based slurry is coated on the current collector to form the cathode, the alkalinity of the slurry is likely to corrode the current collector. Although nickel-containing cathode active materials have high specific capacity, this problem strongly discourages the use of the active material in the water-based manufacturing process of the battery.
[0006] In addition, current lithium-ion battery technology still has other problems that affect the current collector. A typical electrode includes a current collector and an electrode layer located on one or both sides of the current collector; there is an electrode layer-current collector interface where the electrode layer contacts the current collector. The interface is a source of resistance when electrons flow between the electrode layer and the current collector. The interfacial resistance between the electrode layer and the current collector in the battery electrode largely contributes to the overall internal resistance of the battery, which in turn leads to poor electrochemical performance of the battery.
[0007] It is worth noting that the above problems are not unique to lithium-ion batteries. Other types of batteries, such as sodium-ion batteries, also face similar problems.
[0008] In view of the above problems, attempts have been made to reduce damage to a current collector or to reduce interface resistance between an electrode layer and a current collector in a battery electrode.
[0009] U.S. Patent Application Publication No. 20130295458A1 discloses a current collector comprising a metal foil and a layer containing conductive particles, a binder and an organic acid, wherein the layer is located on one or both sides of the metal foil. Polysaccharides and their derivatives are preferred as binders due to their excellent adhesion to metal foils and high ion permeability. The organic acid acts as a crosslinker for the binder, allowing the conductive particles to adhere more firmly to the metal foil. With such a configuration, it is believed that the internal resistance and impedance of the electrochemical element containing the current collector can be reduced. However, the disadvantage of this system is that an additional crosslinker is required to promote the adhesion of the conductive particles to the metal foil; the use of a binder alone is not sufficient to achieve this function. The organic acid is in contact with the metal foil when forming the current collector, and the addition of the organic acid as a crosslinker in the layer is likely to cause the underlying metal foil to corrode over time.
[0010] Therefore, an object of the present invention is to provide a modified current collector for battery electrodes, which is less susceptible to the above-mentioned problems of conventional current collectors and the electrochemical performance of any battery comprising the electrode is also improved. Summary of the invention
[0011] The above-mentioned needs are met by various aspects and embodiments disclosed in the present invention. On the one hand, the present invention provides a modified current collector for a secondary battery, comprising a substrate and a conductive layer coated on one or both sides of the substrate, wherein the conductive layer comprises a conductive material and a binder material, wherein the binder material comprises a copolymer containing a structural unit (a), wherein the structural unit (a) comprises one or more monomer units having formula (1): And wherein R1, R2, R3 and R4 in formula (1) are each independently H, hydroxyl, alkyl or hydroxyalkyl.
[0012] In some embodiments, the copolymer further comprises a structural unit (b), wherein the structural unit (b) comprises one or more monomer units having formula (2): And wherein R5, R6, R7, R8, R9, R 10 and R 11 Each is independently H or alkyl.
[0013] In some embodiments, the copolymer further comprises structural unit (c), wherein structural unit (c) comprises one or more monomer units having formula (3): And R in formula (3) 12 , R 13 , R 14 and R 15 Each is independently H, alkyl, acyloxy or acyloxyalkyl.
[0014] In another aspect, the present invention provides an electrode comprising the modified current collector and an electrode layer located on the surface of a conductive layer, wherein the electrode layer comprises an electrode active material and a binder.
[0015] The invention disclosed in the present invention can solve the above-mentioned problems affecting the current collector in the battery electrode. First, the conductive layer in the modified current collector can serve as a physical barrier between the substrate and the alkaline electrode active material of the electrode layer. This prevents corrosion to the substrate without affecting the conductivity of the electrode. Second, the conductive material in the conductive layer of the modified current collector reduces the interface resistance between the electrode layer and the modified current collector itself, and thus improves the output performance of the electrode.
[0016] In addition, when a water-based electrode slurry is applied to the conductive layer of the modified current collector to form an electrode layer, the binder material in the conductive layer of the modified current collector disclosed in the present invention remains adhered to the substrate and does not dissolve in the electrode slurry, so that peeling of the conductive layer due to dissolution of the binder material does not occur.
[0017] Taking all the above advantages into consideration, the battery comprising the electrode produced by using the modified current collector of the present invention exhibits excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1a and 1b Simplified views showing two different embodiments of the modified current collector disclosed in the present invention in an electrode. DETAILED DESCRIPTION
[0019] -On the one hand, the present invention provides a modified current collector for battery electrodes, wherein the modified current collector comprises a substrate and a conductive layer located on one or both sides of the substrate. The conductive layer itself comprises a binder material and a conductive material, wherein the binder material comprises a suitable copolymer. The conductive layer can be produced by coating a conductive slurry on a substrate, wherein the conductive slurry comprises a conductive material, a binder material and a solvent. On the other hand, the present invention provides an electrode comprising the modified current collector and an electrode layer located on the modified current collector, wherein the electrode layer comprises an electrode active material and a binder, and may further comprise a conductive agent. The electrode layer can be produced by coating an electrode slurry on the modified current collector of the present invention, wherein the electrode slurry comprises an electrode active material, a binder and an aqueous solvent (and an optional conductive agent).
[0020] The term "electrode" refers to either a "cathode" or an "anode".
[0021] The term "electrode component" refers to any substance present in the electrode layer of an electrode, including but not limited to electrode active materials, conductive agents and binders.
[0022] The term "positive electrode" is used interchangeably with cathode. Likewise, the term "negative electrode" is used interchangeably with anode.
[0023] The term "binder", "binder material" or "binder" refers to a chemical compound, a mixture of compounds, or a polymer used to fix a material in place and adhere it to a surface. In some embodiments, a binder material refers to a chemical compound, a mixture of compounds, or a polymer used to fix a conductive material in place and adhere it to a substrate to form a modified current collector. In some embodiments, a binder refers to a chemical compound, a mixture of compounds, or a polymer used to fix an electrode material and / or a conductive agent in place and adhere it to a modified current collector to form an electrode. In some embodiments, the electrode does not contain any conductive material or conductive agent. In some embodiments, the binder material and / or the binder each independently forms a colloid in an aqueous solvent (e.g., water). In some embodiments, the binder material and / or the binder each independently forms a solution or dispersion in an aqueous solvent (e.g., water).
[0024] The term "conductive material" or "conductive agent" refers to a material with good electrical conductivity. Therefore, conductive materials are often added to improve the conductivity of modified current collectors when manufacturing them. In some embodiments, the conductive agent is mixed with the electrode active material when forming the electrode to improve the conductivity of the electrode. In some embodiments, the conductive material and the conductive agent are each independently chemically active. In some embodiments, the conductive material and the conductive agent are each independently chemically inert.
[0025] The term "polymer" refers to a compound prepared by polymerizing monomers, whether of the same or a different type. The generic term "polymer" embraces the terms "homopolymer" and "copolymer."
[0026] The term "homopolymer" refers to a polymer prepared by polymerizing monomers of the same type.
[0027] The term "copolymer" refers to polymers prepared by polymerizing two or more different types of monomers.
[0028] The term "aqueous solvent" refers to a solution containing water as a main component and one or more minor components other than water, or a solution consisting only of water.
[0029] In the case of a slurry, the term "water-based" means that the solvent of the slurry is an aqueous solvent. In the case of a manufacturing method of an electrode or a battery, the term "water-based" means that at least one element of the electrode or battery is formed in whole or in part by using an aqueous slurry.
[0030] The term "unsaturated" refers to a moiety having one or more units of unsaturation.
[0031] The term "alkyl" or "alkyl group" refers to a radical having the general formula C n H 2n+1 A monovalent radical derived from a saturated, unbranched or branched aliphatic hydrocarbon by removing a hydrogen atom, wherein n is an integer.
[0032] The term "cycloalkyl" or "cycloalkyl group" refers to a saturated or unsaturated cyclic non-aromatic hydrocarbon group having a monocyclic or multiple condensed rings. Examples of cycloalkyl groups include, but are not limited to, C3-C7 cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl; C3-C7 cycloalkenyl groups such as cyclopropenyl, cyclobutenyl, cyclopentenyl, cyclohexenyl, and cycloheptenyl; and cyclic terpenes and bicyclic terpenes. The cycloalkyl group may be unsubstituted or substituted with one or two suitable substituents. In addition, the cycloalkyl group may be monocyclic or polycyclic.
[0033] The term "alkenyl" refers to a monovalent group derived from the removal of a hydrogen atom from any carbon atom of an unsaturated aliphatic hydrocarbon having at least one carbon-carbon double bond. Similarly, the term "alkynyl" refers to a monovalent group derived from the removal of a hydrogen atom from any carbon atom of an unsaturated aliphatic hydrocarbon having at least one carbon-carbon triple bond. In addition, the term "alkenynyl" refers to a monovalent group derived from the removal of a hydrogen atom from any carbon atom of an unsaturated aliphatic hydrocarbon having at least one carbon-carbon double bond and at least one carbon-carbon triple bond. The unsaturated aliphatic hydrocarbon of an alkenyl, alkynyl or alkenynyl group may be branched or unbranched.
[0034] The term "alkoxy" refers to an alkyl group as defined above, connected to the main carbon chain by an oxygen atom. Some non-limiting examples of alkoxy groups include methoxy, ethoxy, propoxy, butoxy, etc. And the alkoxy group defined above can be substituted or unsubstituted, wherein the substituent can be, but is not limited to, deuterium, hydroxyl, amino, halogen, cyano, alkoxy, alkyl, alkenyl, alkynyl, mercapto, nitro, etc.
[0035] The term "alkylene" refers to a saturated divalent hydrocarbon group derived from a branched or unbranched saturated hydrocarbon by removing two hydrogen atoms. Examples of alkylene groups include methylene (-CH2-), ethylene (-CH2CH2-), isopropyl (-CH(CH3)CH2-), etc. Alkylene groups are optionally substituted with one or more substituents described herein.
[0036] The term "aryl" or "aryl group" refers to an organic group derived from a monocyclic or polycyclic aromatic hydrocarbon by removing a hydrogen atom. Non-limiting examples of aryl groups include phenyl, naphthyl, benzyl, tolanyl, sexiphenyl, phenanthrenyl, anthracenyl, coronenyl and tolanylphenyl. The aryl group can be unsubstituted or substituted with one or more suitable substituents. In addition, the aryl group can be monocyclic or polycyclic.
[0037] The term "alkylthio" refers to a group containing a branched or unbranched alkyl group connected to a divalent sulfur atom. Non-limiting examples of alkylthio groups include methylthio (CH3S-). Alkylthio groups may be optionally substituted by one or more substituents described herein.
[0038] The term "heteroatom" refers to one or more of oxygen (O), sulfur (S), nitrogen (N), phosphorus (P) or silicon (Si), including any oxidized form of nitrogen (N), sulfur (S) or phosphorus (P); the quaternized form of any basic nitrogen; or a nitrogen in a heterocyclic ring that may be substituted, such as N in 3,4-dihydro-2H-pyrrolyl, NH in pyrrolidinyl, or NR in N-substituted pyrrolidinyl.
[0039] The term "carbonyl" refers to -(C=O)-.
[0040] The term "acyl" refers to -(C=O)-Z, wherein Z is alkyl.
[0041] The term "acyloxy" refers to -O-(C=O)-Z, where Z is alkyl.
[0042] The term "acyloxyalkyl" refers to -YO-(C=O)-Z, where Z is alkyl and Y is alkylene.
[0043] The term "hydroxyalkyl" refers to -YOH, wherein Y is an alkylene group. Thus, the hydroxyalkyl group comprises a hydroxy group bonded to an alkylene group.
[0044] The term "amido" refers to NH(C=O)-R.
[0045] The term "aliphatic" refers to a non-aromatic hydrocarbon or a group derived therefrom. Some non-limiting examples of aliphatic compounds include alkanes, alkenes, alkynes, alkyl groups, alkenyl groups, alkynyl groups, alkylene groups, alkenylene groups, or alkynylene groups.
[0046] The term "aromatic" refers to a group comprising an aromatic hydrocarbon ring, which optionally includes heteroatoms or substituents. Examples of such groups include, but are not limited to, phenyl, tolyl, biphenyl, o-terphenyl, m-terphenyl, p-terphenyl, naphthyl, anthryl, phenanthryl, pyrenyl, triphenylene and derivatives thereof.
[0047] The term "substituted" used to describe a compound or chemical moiety means that at least one hydrogen atom of the compound or chemical moiety is replaced by another chemical moiety. Examples of substituents include, but are not limited to, halogen; alkyl; heteroalkyl; alkenyl; alkynyl; alkenynyl; aryl; heteroaryl; hydroxy; alkoxy; amino; nitro; mercapto; alkylthio; imino; cyano; amide; phosphonato; phosphinato; carboxyl; thiocarbonyl; sulfonyl; sulfonamide; acyl; formyl; acyloxy; alkoxycarbonyl; carbonyl; haloalkyl (e.g., trifluoromethyl); carbocyclic cycloalkyl, which may be a monocyclic or fused or non-fused polycyclic (e.g., cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl) or heterocyclic alkyl, which may be a monocyclic or fused or non-fused polycyclic (e.g., pyrrolidinyl, piperidinyl, piperazinyl, morpholinyl or thiazinyl); carbocyclic or heterocyclic aryl, which may be a monocyclic or fused or non-fused polycyclic (e.g., phenyl, naphthyl, pyrrolyl, indolyl, furanyl, thiophene); 1-(4-(4-phenyl)-2-nitro-1-yl)-2-nitro-1-nitro ... 2; -NH2; -SO2NH2; -OCHF2; -CF3; -OCF3; -NH(alkyl); -N(alkyl)2; -NH(aryl); -N(alkyl)(aryl); -N(aryl)2; -CHO; -CO(alkyl); -CO(aryl); -CO2(alkyl); and -CO2(aryl); and these parts may also be optionally substituted by fused ring structures or bridge structures (e.g., -OCH2O-). These substituents may be optionally further substituted by substituents selected from these groups. Unless otherwise indicated, all chemical groups disclosed in the present invention may be substituted.
[0048] The term "halogen" or "halo" refers to F, Cl, Br or I.
[0049] The term "monomer unit" refers to a constitutional unit derived from a single monomer to the structure of a polymer.
[0050] The term "structural unit" refers to the total monomer units derived from the same monomer type in a polymer.
[0051] The term "homogenizer" refers to a device that can be used to homogenize a material, i.e., to evenly distribute the material throughout a fluid. In the case of the present disclosure of homogenization, any conventional homogenizer can be used for the homogenization process. Some non-limiting examples of homogenizers include a stirring mixer, a planetary mixer, a stirrer, and an ultrasonic generator.
[0052] The term "planetary mixer" refers to a device that can be used to mix or stir different materials to produce a homogenous mixture, which includes a container and a paddle that performs planetary motion in the container. In some embodiments, the planetary mixer includes at least one planetary paddle and at least one high-speed dispersing paddle. The planetary paddle and the high-speed dispersing paddle rotate on their respective axes and also rotate continuously around the container. The rotation speed can be expressed in revolutions per minute (rpm), which refers to the number of revolutions completed by the rotating body in one minute.
[0053] The term "ultrasonicator" refers to a device capable of applying ultrasonic energy to agitate particles in a sample. Some non-limiting examples of ultrasonicators include an ultrasonic bath, a probe-type ultrasonicator, and an ultrasonic flow cell.
[0054] The term "apply" refers to the act of laying or spreading a substance on a surface.
[0055] The term "current collector" refers to any conductive substrate capable of conducting current to an electrode during discharge or charge of a secondary battery. Some non-limiting examples of current collectors include a single metal layer or a single substrate. In some embodiments, the current collector may be in contact with the electrode layer.
[0056] The term "modified current collector" refers to a substrate having a conductive layer applied to one or both sides of the substrate.
[0057] The term "electrode layer" refers to a layer comprising an electrochemically active material. In some embodiments, the electrode layer is in contact with a current collector, a modified current collector, or a substrate. In some embodiments, the electrode layer is made by applying a coating to a current collector, a modified current collector, or a substrate and drying the coating. In some embodiments, the electrode layer is located on the surface of the current collector or the modified current collector. In other embodiments, the three-dimensional porous current collector or the modified current collector is conformally coated with the electrode layer.
[0058] The term "blade coating" refers to a process for producing large-area thin films on rigid or flexible substrates. The coating thickness can be controlled by an adjustable gap width between the coating blade and the coating surface, which allows the deposition of different wet layer thicknesses.
[0059] The term "room temperature" refers to a room temperature of about 18°C to about 30°C, such as 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30°C. In some embodiments, room temperature refers to a temperature of about 20°C + / - 1°C, or + / - 2°C, or + / - 3°C. In other embodiments, room temperature refers to a temperature of about 22°C or about 25°C.
[0060] The term "solids content" refers to the amount of non-volatile matter remaining after evaporation.
[0061] The term "peel strength" refers to the amount of force required to separate two materials that are bonded to each other (e.g., a current collector and an electrode layer). It is a measure of the strength of the bond between the two materials and is usually expressed in N / cm.
[0062] The term "adhesion strength" refers to the amount of force required to separate a substrate and a binder material adhered to the substrate. It is a measure of the strength of the bond between the two materials and is usually expressed in N / cm.
[0063] The term "Ah" refers to the unit used in describing the storage capacity of a battery. For example, a battery with a capacity of 1Ah can provide a current of 1 ampere for 1 hour or a current of 0.5 amperes for two hours, etc. Therefore, 1 Ah is equivalent to 3,600 coulombs of charge. Similarly, the term "milliampere-hour (mAh)" also refers to the unit used in describing the storage capacity of a battery and is 1 / 1,000 of an Ah.
[0064] The term "capacity" is a property of an electrochemical cell and refers to the total amount of charge that an electrochemical cell (e.g., a battery) can hold. Capacity is usually expressed in ampere-hours. The term "specific capacity" refers to the capacity output of an electrochemical cell (e.g., a battery) per unit weight, usually expressed in Ah / kg or mAh / g.
[0065] In the following description, all numerical values disclosed in the present invention are approximate values, regardless of whether the word "about" or "approximately" is used in conjunction with them. They may vary by 1%, 2%, 5% or sometimes 10% to 20%. Whenever a value with a lower limit R is disclosed, L and upper limit R U When a numerical range of R=R is specified, any value within the range is specifically disclosed. Specifically, the following values within the range are specifically disclosed: L +k*(R U -R L ), wherein k is a variable from 0% to 100%. Also, any numerical range defined by two R values determined in the above manner is also specifically disclosed.
[0066] In this specification, all cases where the singular is used also include cases where the plural is used, and vice versa. In this specification, where the context permits, reference to "aqueous solvent" may also specifically refer to water.
[0067] Battery electrodes typically include a current collector and an electrode layer on one or both sides of the current collector. Typically, electrodes are prepared by dispersing an electrode active material and a binder in a solvent to form an electrode slurry, which is then coated on a current collector and dried to form an electrode layer. The electrode slurry (and the electrode layer thus prepared) may additionally include conductive carbon. Regardless of the components present in the electrode layer, the discontinuity between the electrode layer and the current collector in the electrode means that there is a significant interface resistance between the electrode layer and the current collector. Due to this interface resistance, a battery containing such an electrode will have suboptimal electrochemical performance.
[0068] Among batteries, lithium-ion batteries are some of the most widely studied and used. One common component of an electrode slurry used in lithium-ion batteries includes PVDF as a binder and NMP as a solvent, but the use of NMP poses significant environmental, health, and safety risks in addition to the additional costs associated with the recycling system. Therefore, the use of water-based electrode slurries including aqueous solvents (e.g., water) has been proposed as an alternative.
[0069] However, corrosion of the current collector is particularly significant in cathodes produced using water-based slurries containing nickel-containing cathode active materials (eg, NMC) because such slurries can be relatively alkaline.
[0070] In order to solve the above problems, the inventors of the present invention proposed the use of a novel modified current collector, which comprises a substrate and a conductive layer located on one or both sides of the substrate. In the battery electrode, the conductive layer of the modified current collector disclosed in the present invention reduces the interface resistance between the electrode layer and the modified current collector, and acts as a physical barrier between the substrate and the electrode layer, which helps to reduce the tendency of substrate corrosion. In addition, the conductive layer of the present invention has the advantage of not being reduced to liquid when a water-based electrode slurry is applied to the conductive layer.
[0071] The modified current collector described in the present invention refers to a substrate having a conductive layer applied on one or both sides of the substrate, wherein the conductive layer comprises a conductive material and a binder material. Figure 1a A simplified diagram of an embodiment of a modified current collector of the present invention is shown, denoted by 10 in electrode 100. Modified current collector 10 comprises substrate 101, and conductive layer 102 is applied to one side of substrate 101. In the production of battery electrodes, electrode layer 20 may be located on the surface of conductive layer 102.
[0072] Figure 1bA simplified diagram of another embodiment of a modified current collector of the present invention is shown, represented by 11 in electrode 110. Modified current collector 11 comprises substrate 111 and conductive layers 112a and 112b applied on both sides of substrate 111. In the process of manufacturing battery electrodes, electrode layers 21a and 21b may be applied on the surfaces of conductive layers 112a and 112b, respectively.
[0073] When used in a battery system, the substrate in the modified current collector of the present invention is specifically used to collect electrons generated by the electrochemical reaction of the cathode active material or to provide electrons required for the electrochemical reaction.
[0074] In some embodiments, the substrate may be in the form of a foil, sheet, film, or porous body having a three-dimensional network structure. In some embodiments, the substrate may be made of a polymer or a metallic material or a metallized polymer. In some embodiments, the substrate is covered with a conformal carbon layer. In some embodiments, the substrate is made of a single material. In other embodiments, the substrate is made of more than one material.
[0075] In some embodiments, the substrate is a metal. In some embodiments, the substrate has a single layer structure. In some embodiments, the substrate is selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, alloys thereof, conductive resins, and combinations thereof.
[0076] In certain embodiments, the substrate has a two-layer structure including an outer layer and an inner layer, wherein the outer layer includes a conductive additive and the inner layer includes an insulating material or another conductive additive; for example, aluminum covered with a conductive resin layer or a polymer insulating material coated with an aluminum layer. In some embodiments, the conductive additive is selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, alloys thereof, conductive resins, and combinations thereof.
[0077] In some embodiments, the substrate has a three-layer structure including an outer layer, an intermediate layer, and an inner layer, wherein the outer layer and the inner layer include a conductive additive, and the intermediate layer includes an insulating material or another conductive additive; for example, plastic coated with a metal film on both sides. In certain embodiments, each of the outer layer, the intermediate layer, and the inner layer is independently selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, alloys thereof, conductive resins, and combinations thereof.
[0078] In some embodiments, the insulating material is a polymer material selected from the group consisting of polycarbonate, polyacrylate, polyacrylonitrile, polyester, polyamide, polystyrene, polyurethane, polyepoxy, poly(acrylonitrile butadiene styrene), polyimide, polyolefin, polyethylene, polypropylene, polyphenylene sulfide, poly(vinyl ester), polyvinyl chloride, polyether, polyphenylene oxide, cellulosic polymers, and combinations thereof. In certain embodiments, the substrate has more than three layers.
[0079] In the battery electrode comprising the modified current collector and electrode layer of the present invention, the conductive material in the conductive layer of the modified current collector provides a conductive path for the electrons flowing between the electrode layer and the substrate of the modified current collector. This significantly reduces the interface resistance between the electrode layer and the modified current collector, i.e., at the electrode layer-modified current collector interface.
[0080] In some embodiments, the conductive material in the conductive layer is a carbonaceous material selected from the group consisting of natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesophase carbon microbeads (MCMB), carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon tubes, carbon nanotubes, activated carbon, Super P, KS6, vapor-grown carbon fibers (VGCF), mesoporous carbon, and combinations thereof. Using a combination of conductive materials with different particle sizes can improve stacking and thus increase the conductivity of the conductive material, further improving battery performance.
[0081] In a battery electrode comprising the modified current collector and electrode layer of the present invention, the binder material in the conductive layer of the modified current collector provides adhesion between components within the conductive layer and to the substrate.
[0082] In some embodiments, the binder material in the conductive layer comprises a copolymer. In some embodiments, the copolymer comprises structural unit (a), structural unit (b), and structural unit (c).
[0083] In some embodiments, the structural unit (a) in the copolymer of the binder material comprises one or more monomer units having formula (1):
[0084] In some embodiments, R1, R2, R3 and R4 in formula (1) are each independently H, hydroxyl, alkyl, hydroxyalkyl, halogen or haloalkyl. In certain embodiments, at least one of R1, R2, R3 and R4 is hydroxyl or hydroxyalkyl. In some embodiments, at least two of R1, R2, R3 and R4 are the same. In other embodiments, R1, R2, R3 and R4 are each different.
[0085] In some embodiments, the alkyl group has the general formula CnH 2n+1, wherein n is an integer between 1 and 40, between 1 and 20, or between 1 and 8. In some embodiments, the alkyl group can be selected from C1-C 40 Alkyl groups, C1-C 30 Alkyl groups, C1-C 20 Alkyl groups, C1-C 10 Alkyl groups, C1-C8 alkyl groups, C5-C 40 Alkyl groups, C5-C 30 Alkyl groups, C5-C 20 Alkyl groups, C5-C 10 Alkyl group, C5-C8 alkyl group, C 10 -C 40 Alkyl group, C 10 -C 30 Alkyl groups and C 10 -C 20 The group consisting of alkyl groups.
[0086] The example of alkyl group includes but is not limited to methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, 3-methyl-1-pentyl, 4-methyl-1-pentyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 2,2-dimethyl-1-butyl, 3,3-dimethyl-1-butyl, 2-ethyl-1-butyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, neopentyl, hexyl, heptyl and octyl. Longer alkyl groups include nonyl and decyl groups. Alkyl groups can be unsubstituted or substituted by one or more suitable substituents. In addition, alkyl groups can be branched or unbranched. In some embodiments, the alkyl group contains at least 2, 3, 4, 5, 6, 7, or 8 carbon atoms.
[0087] In some embodiments, the hydroxyalkyl group can be selected from the group consisting of C1-C 40 Hydroxyalkyl groups, C1-C 30 Hydroxyalkyl groups, C1-C 20 Hydroxyalkyl groups, C1-C 10 Hydroxyalkyl groups, C1-C8 hydroxyalkyl groups, C5-C 40 Hydroxyalkyl groups, C5-C 30 Hydroxyalkyl groups, C5-C 20 Hydroxyalkyl groups, C5-C 10 Hydroxyalkyl groups, C5-C8 hydroxyalkyl groups, C 10 -C 40 Hydroxyalkyl groups, C 10 -C30 Hydroxyalkyl groups and C 10 -C 20 The group consisting of hydroxyalkyl groups.
[0088] Examples of hydroxyalkyl groups include, but are not limited to, hydroxymethyl, hydroxyethyl, hydroxypropyl, hydroxymethylpropyl, hydroxybutyl and hydroxymethylbutyl, hydroxydimethylpropyl, hydroxymethylpentyl, hydroxydimethylbutyl, hydroxyethylbutyl, hydroxypentyl, hydroxyneopentyl, hydroxyhexyl, hydroxyheptyl and hydroxyoctyl. The alkyl group in the hydroxyalkyl group can be branched or unbranched.
[0089] In some embodiments, the halogen may be selected from the group consisting of fluorine, chlorine, bromine, iodine, astatine, and combinations thereof.
[0090] Some non-limiting examples of haloalkyl include fluoromethyl, chloromethyl, bromomethyl, iodomethyl, astatomethyl, fluoroethyl, chloroethyl, bromoethyl, iodoethyl, astatoethyl, fluoropropyl, chloropropyl, bromopropyl, iodopropyl, and astatopropyl.
[0091] Typically, structural unit (a) should be polar in nature to promote the dispersion of the binder material in the polar solvent of the conductive paste. For this reason, R1, R2, R3 and R4 in the formula (1) of the monomer unit in the structural unit (a) are unlikely to each independently contain a long hydrocarbon chain. The presence of too many long hydrocarbon chains in the monomer unit of the structural unit (a) will cause the structural unit (a) to lose polarity, potentially affecting the overall dispersibility of the binder material in the conductive paste and the homogeneity of the conductive layer. This will not only lead to inconsistent adhesion across the substrate-conductive layer interface, but also the conductive network formed to promote the flow of electrons between the electrode layer and the substrate will be severely weakened, which will aggravate the interface resistance between the electrode layer and the modified current collector.
[0092] At the same time, it is undesirable that all R1, R2, R3 and R4 in the formula (1) of the monomer unit in the structural unit (a) are hydroxyl or hydroxyalkyl. The structural unit (a) containing excessive hydroxyl or hydroxyalkyl groups may cause excessive hydrogen bond interactions between hydroxyl groups and / or hydroxyalkyl groups within the copolymer chain and between different copolymer chains. This will result in agglomeration of the resulting binder material and other materials (such as conductive materials) in the conductive paste when producing the conductive layer, and the dispersibility is also poor. In some embodiments, at most three of R1, R2, R3 and R4 are hydroxyl or hydroxyalkyl. In certain embodiments, at most two of R1, R2, R3 and R4 are hydroxyl or hydroxyalkyl. In certain embodiments, at most one of R1, R2, R3 and R4 is hydroxyl or hydroxyalkyl. In certain embodiments, only one of R1, R2, R3 and R4 is hydroxyl, and the remaining three of R1, R2, R3 and R4 are independently alkyl or H. In a further embodiment, only one of R1, R2, R3 and R4 is hydroxyl, and the remaining three of R1, R2, R3 and R4 are each independently H.
[0093] In some embodiments, the structural unit (b) in the copolymer of the binder material comprises one or more monomer units having formula (2):
[0094] In some embodiments, R5, R6, R7, R8, R9, R 10 and R 11 Each is independently H, alkyl, halogen or haloalkyl. 11 In some embodiments, R5, R6, R7, R8, R9, R 10 and R 11 In other embodiments, at least two of R5, R6, R7, R8, R9, R 10 and R 11 Each is different.
[0095] Generally, the structural unit (b) should have low polarity, but it is not suitable to make most of R5, R6, R7, R8, R9, R 10 and R 11 The long hydrocarbon chains are included to reduce the polarity of the structural unit (b). Too many long hydrocarbon chains in the monomer units in the structural unit (b) will lead to poor interaction between the structural unit (b) and the polar solvent in the conductive paste and promote the agglomeration of the entire copolymer chain. Different copolymer chains may also be entangled to form a compact spherical structure. Therefore, too many long hydrocarbon chains in the structural unit (b) will hinder the full dispersion of the binder material and other materials in the conductive paste. In some embodiments, R5, R6, R7, R8, R9, R10 and R 11 The majority of R5, R6, R7, R8, R9, R 10 and R 11 In certain embodiments, R5, R6, R7, R8, R9, R 10 and R 11 In certain embodiments, only R 11 is an alkyl group, and R5, R6, R7, R8, R9 and R 10 are each independently H. In some embodiments, only R 11 is propyl, and R5, R6, R7, R8, R9 and R 10 Each is independently H. In certain embodiments, R5, R6, R7, R8, R9, R 10 and R 11 One or more of the is a C1-C8 alkyl group.
[0096] In some embodiments, the structural unit (c) in the copolymer of the binder material comprises one or more monomer units having formula (3):
[0097] In some embodiments, R in formula (3) 12 , R 13 , R 14 and R 15 Each is independently H, alkyl, acyloxy, acyloxyalkyl, halogen or haloalkyl. 12 , R 13 , R 14 and R 15 At least one is acyloxy or acyloxyalkyl. 12 , R 13 , R 14 and R 15 At least two are the same. In other embodiments, R 12 , R 13 , R 14 and R 15 Each is different.
[0098] As defined above, an acyloxy group has the structure -O-(C=O)-Z, wherein Z refers to an alkyl group, and an acyloxyalkyl group has the structure -YO-(C=O)-Z, wherein Y refers to an alkylene group, and Z refers to an alkyl group.
[0099] In some embodiments, the alkyl group Z in each acyloxy group or acyloxyalkyl group can be independently selected from C1-C40 Alkyl groups, C1-C 30 Alkyl groups, C1-C 20 Alkyl groups, C1-C 10 Alkyl group, C1-C8 alkyl group, C1-C5 alkyl group, C5-C 40 Alkyl groups, C5-C 30 Alkyl groups, C5-C 20 Alkyl groups, C5-C 10 Alkyl group, C 10 -C 40 Alkyl group, C 10 -C 30 Alkyl groups and C 10 -C 20 The group consisting of alkyl groups.
[0100] The example of the alkyl group in each acyloxy group or acyloxyalkyl group includes but is not limited to C1-C8 alkyl group, for example methyl, ethyl, propyl, isopropyl, 2-methyl isophthalic acid-propyl group, 2-methyl-2-propyl group, 2-methyl isophthalic acid-butyl group, 3-methyl isophthalic acid-butyl group, 2-methyl-3-butyl group, 2,2-dimethyl-1-propyl group, 2-methyl isophthalic acid-pentyl group, 3-methyl isophthalic acid-pentyl group, 4-methyl-1-pentyl group, 2-methyl-2-pentyl group, 3-methyl-2-pentyl group, 4-methyl-2-pentyl group, 2,2-dimethyl-1-butyl group, 3,3-dimethyl-1-butyl group, 2-ethyl-1-butyl group, butyl, isobutyl group, the tert-butyl group, amyl group, isopentyl group, neopentyl group, hexyl group, heptyl group and octyl group. Longer alkyl group includes nonyl and decyl group. Alkyl group can be unsubstituted or replaced by one or more suitable substituents. In addition, the alkyl group can be branched or unbranched.In some embodiments, the alkyl group contains at least 2, 3, 4, 5, 6, 7 or 8 carbon atoms.
[0101] In some embodiments, the alkylene group Y in the acyloxyalkyl group can be independently selected from C1-C 40 Alkylene group, C1-C 30 Alkylene group, C1-C 20 Alkylene group, C1-C 10 Alkylene group, C1-C8 alkylene group, C1-C5 alkylene group, C5-C 40 Alkylene group, C5-C 30 Alkylene group, C5-C 20 Alkylene group, C5-C 10 Alkylene group, C 10 -C 40 Alkylene group, C 10 -C 30 Alkylene group and C10 -C 20 The group that alkylene group forms.The alkylene group in acyloxyalkyl group can be branched or unbranched.The example of alkylene group in acyloxyalkyl group includes but not limited to methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, decylene, sub-undecylene, sub-dodecylene, sub-tridecylene, sub-tetradecylene, sub-pentadecylene, sub-hexadecylene, sub-heptadecylene, sub-octadecylene, sub-nonadecylene, sub-eicosylene and stereoisomer thereof.Some non-limiting examples of acyloxyalkyl group include acyloxymethyl, acyloxyethyl, acyloxypropyl, acyloxy (methyl) propyl group and acyloxy (methyl) butyl.
[0102] For the present invention, structural unit (c) is optional; structural unit (a) and structural unit (b) are sufficient to provide the desired properties of the binder (e.g., good bonding strength, dispersibility in polar solvents, and resistance to redissolution in aqueous solvents). However, it is found that the addition of structural unit (c) to the binder material helps to further improve the modified current collector by increasing the flexibility of the current collector. Therefore, it is preferred that structural unit (c) is present in the binder material of the conductive layer. The flexibility of the modified current collector can be measured by any known method, for example, Chinese National Standard GB / T 1731-93.
[0103] For the same reason as for the structural unit (b), most of the R 12 , R 13 , R 14 and R 15 It is also undesirable to include long hydrocarbon chains. 12 , R 13 , R 14 and R 15 The majority of is H. In some embodiments, R 12 , R 13 , R 14 and R 15 At most three are alkyl, acyloxy or acyloxyalkyl. 12 , R 13 , R 14 and R 15 At most two are alkyl, acyloxy or acyloxyalkyl. 12 , R 13 , R 14 and R 15 Only one is acyloxy or acyloxyalkyl. 12 , R 13 , R 14 and R15 Only one is acetoxy, and R 12 , R 13 , R 14 and R 15 The remaining three are each independently alkyl or H.
[0104] In some embodiments, the proportion of structural unit (a) in the copolymer of the binder material is about 5% to about 20%, about 8% to about 20%, about 10% to about 20%, about 12% to about 20%, about 15% to about 20%, about 18% to about 20%, about 20% to about 30%, about 5% to about 28%, about 8% to about 28%, about 10% to about 18%, about 12% to about 18%, about 20% to about 30%, about 5% to about 28%, about 8% to about 28%, about 10% to about 18%, about 12% to about 18%, about 15% to about 18%, about 12% to about 18%, about 14% to about 18%, about 5% to about 16%, about 8% to about 16%, about 10% to about 16%, about 12% to about 16%, about 5% to about 14%, about 8% to about 14%, about 10% to about 14%, about 12% to about 14%, about 5% to about 12%, about 8% to about 12%, about 10% to about 12%, about 5% to about 10%, about 8% to about 10%, about 5% to about 8%.
[0105] In some embodiments, the proportion of structural unit (a) in the copolymer of the binder material is less than 20%, less than 19.5%, less than 19%, less than 18.5%, less than 18%, less than 17.5%, less than 17%, less than 16.5%, less than 16%, less than 15.5%, less than 15%, less than 14.5%, less than 14%, less than 13.5%, less than 13%, less than 12.5% or less than 12% by mole, based on the total moles of monomer units in the copolymer. In some embodiments, the proportion of structural unit (a) in the copolymer of the binder material is at least 10%, at least 10.5%, at least 11%, at least 11.5%, at least 12%, at least 12.5%, at least 13%, at least 13.5%, at least 14%, at least 14.5%, at least 15%, at least 15.5%, at least 16%, at least 16.5%, at least 17%, at least 17.5%, at least 18%, at least 18.5%, at least 19%, at least 19.5%, at least 20% by mole, based on the total moles of monomer units in the copolymer.
[0106] In some embodiments, the proportion of structural unit (b) in the copolymer of the binder material is about 80% to about 90%, about 80.5% to about 90%, about 81% to about 90%, about 81.5% to about 90%, about 82% to about 90%, about 82.5% to about 90%, about 83% to about 90%, about 83.5% to about 90%, about 84% to about 90%, about 84.5% to about 90%, about 86% to about 90%, about 87% to about 90%, about 88% to about 90%, about 89% to about 90%, about 91% to about 90%, about 92% to about 90%, about 93% to about 90%, about 94% to about 90%, about 95% to about 90%, about 96% to about 90%, about 97% to about 90%, about 98% to about 90%, about 99% to about 90%, about 100% to about 100%, about 101% to about 100%, about 102% to about 100%, about 103% to about 100%, about 104% to about 100%, about 105% to about 100%, about 106% to about 100%, about 107% to about 100%, about 108% to about 100%, about 109% to about 101%, about 110% to about 110%, about 111% to about 110%, about 112% to about 113%, about 113% to about 114%, about 114% to about 115%, about 115% to about 116%, about 116% to about 117%, about 85% to about 90%, about 85.5% to about 90%, about 86% to about 90%, about 86.5% to about 90%, about 87% to about 90%, about 80% to about 89%, about 80.5% to about 89%, about 81% to about 89%, about 81.5% to about 89%, about 82% to about 89%, about 82.5% to about 89%, about 83% to about 89%, about 83.5% to about 89%, about 84% to about 89%, about 84.5% to about 89% , about 85% to about 89%, about 85.5% to about 89%, about 86% to about 89%, about 80% to about 88%, about 80.5% to about 88%, about 81% to about 88%, about 81.5% to about 88%, about 82% to about 88%, about 82.5% to about 88%, about 83% to about 88%, about 83.5% to about 88%, about 84% to about 88%, about 84.5% to about 88%, about 85% to about 88%, about 80% to about 86% , about 80.5% to about 86%, about 81% to about 86%, about 81.5% to about 86%, about 82% to about 86%, about 82.5% to about 86%, about 83% to about 86%, about 80% to about 85%, about 80.5% to about 85%, about 81% to about 85%, about 81.5% to about 85%, about 82% to about 85%, about 80% to about 83%, about 80.5% to about 83%, about 81% to about 83%, or about 80% to about 82%.
[0107] In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (b) in the copolymer of the binder material is less than 90%, less than 89.5%, less than 89%, less than 88.5%, less than 88%, less than 87.5%, less than 87%, less than 86.5%, less than 86%, less than 85.5%, less than 85%, less than 84.5%, less than 84%, less than 83.5%, less than 83%, less than 82.5% or less by mole. In some embodiments, the proportion of structural unit (b) in the copolymer of the binder material is at least 80%, at least 80.5%, at least 81%, at least 81.5%, at least 82%, at least 82.5%, at least 83%, at least 83.5%, at least 84%, at least 84.5%, at least 85%, at least 85.5%, at least 86%, at least 86.5%, at least 87%, at least 87.5% or at least 88% by mole, based on the total moles of monomer units in the copolymer.
[0108] In some embodiments, the copolymer of the binder material does not contain the structural unit (c). In other embodiments, the proportion of the structural unit (c) in the copolymer of the binder material is about 0.1% to about 5%, about 0.1% to about 4.5%, about 0.1% to about 4%, about 0.1% to about 3.5%, about 0.1% to about 3%, about 0.1% to about 2.8%, about 0.1% to about 2.6%, about 0.1% to about 2.5%, about 0.1% to about 2.4%, about 0.1% to about 2.3%, about 0.1% to about 2.2%, about 0.1% to about 2.1%, about 0.1% to about 2.8%, about 0.1% to about 2.6%, about 0.1% to about 2.5%, about 0.1% to about 2.4%, about 0.1% to about 2.3%, about 0.1% to about 2.2%, about 0.1% to about 2.1%, about 0.1% to about 2.1%. to about 2%, about 0.1% to about 1.9%, about 0.1% to about 1.8%, about 0.1% to about 1.7%, about 0.1% to about 1.6%, about 0.1% to about 1.5%, about 0.1% to about 1.4%, about 0.1% to about 1.3%, about 0.1% to about 1.2%, about 0.1% to about 1.1%, about 0.1% to about 1%, about 0.5% to about 5%, about 0.5% to about 4.5%, about 0.5% to about 4%, about 0.5% to about 3.5%, about 0.5% to about 3%, about 0.5% to about 2.8%, about 0.5% to about 2.6%, about 0.5% to about 2.5%, about 0.5% to about 2.4%, about 0.5% to about 2.3%, about 0.5% to about 2.2%, about 0.5% to about 2.1%, about 0.5% to about 2%, about O.5% to about 1.9%, about O.5% to about 1.8%, about O.5% to about 1.7%, about O.5% to about 1.6%, about O.5% to about 1.5%, about 1% to about 5%, about 1% to about 4.5%, about 1% to about 4%, about 1% to about 3.5%, about 1% to about 3%, about 1% to about 2.8%, about 1% to about 2 .6%, about 1% to about 2.5%, about 1% to about 2.4%, about 1% to about 2.3%, about 1% to about 2.2%, about 1% to about 2.1%, about 1% to about 2%, about 1.5% to about 5%, about 1.5% to about 4.5%, about 1.5% to about 4%, about 1.5% to about 3.5%, about 1.5% to about 3%, about 1.5% to about 2.8%, about 1.5% to about 2.6%, about 1.5% to about 2.5%, about 2% to about 5%, about 2% to about 4.5%, about 2% to about 4%, about 2% to about 3.5% or about 2% to about 3.
[0109] In some embodiments, the proportion of structural unit (c) in the copolymer of the binder material is less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2.4%, less than 2.3%, less than 2.2%, less than 2.1%, less than 2%, less than 1.9%, less than 1.8%, less than 1.7%, less than 1.6%, less than 1.5%, less than 1.4%, less than 1.3%, less than 1.2%, less than 1.1% or less than 1% by mole, based on the total moles of monomer units in the copolymer. In some embodiments, the proportion of structural unit (c) in the copolymer of the binder material is at least 0.1%, at least 0.5%, at least 1%, at least 1.1%, at least 1.2%, at least 1.3%, at least 1.4%, at least 1.5%, at least 1.6%, at least 1.7%, at least 1.8%, at least 1.9%, at least 2%, at least 2.1%, at least 2.2%, at least 2.3%, at least 2.4%, at least 2.5% or at least 3% by mole, based on the total moles of monomer units in the copolymer.
[0110] The relative ratio of structural unit (b) to structural unit (a) in the copolymer of the binder material is critical for controlling the functionality of the binder material (i.e., adhesion strength, dispersibility in polar solvents, and anti-redissolution ability in aqueous solvents). When the molar ratio of structural unit (b) to structural unit (a) in the copolymer of the binder material is within the scope disclosed in the present invention, it is observed that the binder material exhibits excellent adhesion strength. In addition, the binder material can also be uniformly dispersed in a polar solvent, allowing the conductive paste containing the binder material to be easily processed during the manufacture of the modified current collector. Most importantly, the binder material exhibits a high level of anti-redissolution ability in an aqueous solvent. This is particularly significant when an electrode layer slurry is applied to form an electrode on the surface of a conductive layer containing a binder material. It is observed that the binder material disclosed in the present invention can maintain its ability to adhere the conductive layer to the substrate when in contact with an aqueous solvent without being reduced to a fluid. This keeps the conductive layer intact on the substrate, thereby forming a physical barrier between the substrate and the electrode layer, and thus helps to reduce the possibility of substrate corrosion. The presence of this conductive layer reduces the interfacial resistance between the electrode layer and the modified current collector, thereby improving the electrochemical performance of the battery.
[0111] In some embodiments, the molar ratio of structural unit (b) to structural unit (a) in the copolymer of the binder material is from about 4 to about 15, from about 4.5 to about 15, from about 5 to about 15, from about 5.5 to about 15, from about 6 to about 15, from about 6.5 to about 15, from about 7 to about 15, from about 7.5 to about 15, from about 8 to about 15, from about 8.5 to about 15, from about 9 to about 15, from about 9.5 to about 15, from about 10 to about 15, from about 12 to about 15, from about 4 to about 12, from about 4.5 to about 12, from about 5 to about 12, from about 5.5 to about 12, From about 6 to about 12, from about 6.5 to about 12, from about 7 to about 12, from about 7.5 to about 12, from about 8 to about 12, from about 8.5 to about 12, from about 9 to about 12, from about 9.5 to about 12, from about 10 to about 12, from about 4 to about 10, from about 4.5 to about 10, from about 5 to about 10, from about 5.5 to about 10, from about 6 to about 10, from about 6.5 to about 10, from about 7 to about 10, from about 7.5 to about 10, from about 8 to about 10, from about 4 to about 8, from about 4.5 to about 8, from about 5 to about 8, from about 5.5 to about 8, from about 6 to about 8, or from about 4 to about 6.
[0112] In some embodiments, the molar ratio of structural unit (b) to structural unit (a) in the copolymer of the binder material is less than 15, less than 12, less than 10, less than 9, less than 8.5, less than 8, less than 7.5, less than 7, less than 6.5, less than 6, less than 5.5, or less than 5. In some embodiments, the molar ratio of structural unit (a) to structural unit (b) in the copolymer of the binder material is greater than 4, greater than 4.5, greater than 5, greater than 5.5, greater than 6, greater than 6.5, greater than 7, greater than 7.5, greater than 8, greater than 8.5, greater than 9, greater than 9, greater than 9.5, greater than 10, or greater than 12.
[0113] The weight average molecular weight (Mw) of the copolymer in the binder material greatly affects the adhesion strength of the copolymer, which affects the ability of the conductive layer to remain adhered to the substrate. This affects the mechanical strength of the modified current collector (and the electrode produced therefrom) and the ability of the conductive layer to prevent corrosion of the substrate. When the weight average molecular weight of the copolymer in the binder material falls within the following range, the adhesion strength of the copolymer will be improved.
[0114] In some embodiments, the weight average molecular weight of the copolymer in the binder material is about 50,000 g / mol to about 300,000 g / mol, about 60,000 g / mol to about 300,000 g / mol, about 80,000 g / mol to about 300,000 g / mol, about 90,000 g / mol to about 300,000 g / mol, about 100,000 g / mol to about 300,000 g / mol, about 120,000 g / mol to about 300,000 g / mol, about 150,000 g / mol to about 300,000 g / mol, about 170,000 g / mol to about 300,000 g / mol, or about 180,000 g / mol to about 300,000 g / mol. g / mol to about 270,000 g / mol, about 90,000 g / mol to about 270,000 g / mol, about 100,000 g / mol to about 270,000 g / mol, about 120,000 g / mol to about 270,000 g / mol, about 150,000 g / mol to about 270,000 g / mol, about 200,000 g / mol to about 200,000 g / mol, about 220,000 g / mol to about 300,000 g / mol, about 50,000 g / mol to about 270,000 g / mol, about 60,000 g / mol to about 270,000 g / mol, about 80,000 g / mol to about 270,000 g / mol, about 90,000 g / mol to about 270,000 g / mol, about 100,000 g / mol to about 270,000 g / mol, about 120,000 g / mol to about 270,000 g / mol000 g / mol, about 150,000 g / mol to about 270,000 g / mol, about 170,000 g / mol to about 270,000 g / mol, about 200,000 g / mol to about 270,000 g / mol, about 220,000 g / mol to about 270,000 g / mol, about 50,000 g / mol to about 250,000 g / mol, about 60,000 g / mol to about 250,000 g / mol, about 80,000 g / mol to about 250,000 g / mol , about 90,000 g / mol to about 250,000 g / mol, about 100,000 g / mol to about 250,000 g / mol, about 120,000 g / mol to about 250,000 g / mol, about 150,000 g / mol to about 250,000 g / mol, about 170,000 g / mol to about 250,000 g / mol, about 200,000 g / mol to about 250,000 g / mol, about 50,000 g / mol to about 200,000 g / mol, about 60,000 g / mol to about 250,000 g / mol g / mol to about 200,000 g / mol, about 80,000 g / mol to about 200,000 g / mol, about 90,000 g / mol to about 200,000 g / mol, about 100,000 g / mol to about 200,000 g / mol, about 120,000 g / mol to about 200,000 g / mol, about 150,000 g / mol to about 200,000 g / mol, about 50,000 g / mol to about 170,000 g / mol, about 60,000 g / mol to about 170 ,000 g / mol, about 80,000 g / mol to about 170,000 g / mol, about 90,000 g / mol to about 170,000 g / mol, about 100,000 g / mol to about 170,000 g / mol, about 120,000 g / mol to about 170,000 g / mol, about 80,000 g / mol to about 150,000 g / mol, about 90,000 g / mol to about 150,000 g / mol, or about 100,000 g / mol to about 150,000 g / mol.
[0115] In some embodiments, the weight average molecular weight of the copolymer in the binder material is less than 300,000 g / mol, less than 270,000 g / mol, less than 250,000 g / mol, less than 220,000 g / mol, less than 200,000 g / mol, less than 170,000 g / mol, less than 150,000 g / mol, less than 120,000 g / mol or less than 100,000 g / mol. In some embodiments, the weight average molecular weight of the copolymer in the binder material is greater than 80,000 g / mol, greater than 90,000 g / mol, greater than 100,000 g / mol, greater than 120,000 g / mol, greater than 150,000 g / mol, greater than 170,000 g / mol, greater than 200,000 g / mol, greater than 220,000 g / mol or greater than 250,000 g / mol.
[0116] The binder material used in the present invention exhibits a strong adhesion ability, which ensures that the conductive layer is firmly adhered to the substrate, and therefore the modified current collector of the present invention (and the electrode produced thereby) will have excellent mechanical strength. In some embodiments, the adhesion strength between the binder material and the substrate is about 2N / cm to about 8N / cm, about 2N / cm to about 7N / cm, about 2N / cm to about 6N / cm, about 2N / cm to about 5N / cm, about 2N / cm to about 4N / cm, about 2N / cm to about 3N / cm, about 3N / cm to about 8N / cm, about 4N / cm to about 8N / cm, about 5N / cm to about 8N / cm or about 6N / cm to about 8N / cm.
[0117] In some embodiments, the adhesive strength between the binder material and the substrate is less than 8 N / cm, less than 7 N / cm, less than 6 N / cm, less than 5 N / cm, less than 4 N / cm, or less than 3 N / cm. In some embodiments, the adhesive strength between the binder material and the substrate is greater than 2 N / cm, greater than 3 N / cm, greater than 4 N / cm, greater than 5 N / cm, greater than 6 N / cm, or greater than 7 N / cm.
[0118] The proportion of the binder material and the conductive material in the conductive layer of the modified current collector has a huge impact on the effective formation of a stable conductive layer structure of the conductive layer, reduces the tendency of substrate corrosion, and minimizes the interface resistance between the electrode layer and the modified current collector. Insufficient amount of conductive material in the conductive layer may lead to the formation of a conductive network whose coverage is not enough to promote effective electron flow between the electrode layer and the substrate, which may increase the interface resistance. On the other hand, insufficient amount of binder material in the conductive layer may make it difficult to fix the entire conductive layer in place. When subjected to slight changes in the external environment (e.g., scratches, pressure, etc.), the conductive layer may be easily decomposed, and the internal components will separate. Problems related to substrate corrosion may therefore persist.
[0119] In some embodiments, the binder material and the conductive material are present in the conductive layer of the modified current collector in an amount independently of one another by weight, based on the total weight of the conductive layer, of about 20% to about 80%, about 25% to about 80%, about 30% to about 80%, about 35% to about 80%, about 40% to about 80%, about 45% to about 80%, about 50% to about 80%, about 55% to about 80%, about 60% to about 80%, about 20% to about 75%, about 25% to about 75%, about 30% to about 75%, about 35% to about 75%, about 40% to about 75%, about 45% to about 75%, about 50% to about 75%, about 55% to about 75%, about 60% to about 75%, about 20% to about 70%, about 25% to about 70%, about 30% to about 70%, about 35% to about 75%, about 40% to about 75%, about 45% to about 75%, about 50% to about 75%, about 55% to about 75%, about 60% to about 75%, about 20% to about 70%, about 25% to about 70%, about 30% to about 70%, about 35% to about 75%, about From about 1% to about 70%, from about 40% to about 70%, from about 45% to about 70%, from about 50% to about 70%, from about 55% to about 70%, from about 20% to about 65%, from about 25% to about 65%, from about 30% to about 65%, from about 35% to about 65%, from about 40% to about 65%, from about 45% to about 65%, from about 50% to about 65%, from about 20% to about 60%, from about 25% to about 60%, from about 30% to about 60%, from about 35% to about 60%, from about 40% to about 60%, from about 45% to about 60%, from about 20% to about 55%, from about 25% to about 55%, from about 30% to about 55%, from about 35% to about 55%, from about 40% to about 55%, from about 20% to about 50%, from about 25% to about 50%, from about 30% to about 50% or from about 35% to about 50%.
[0120] In some embodiments, based on the total weight of the conductive layer, the proportion of the binder material and the conductive material in the conductive layer of the modified current collector is independently less than 75%, less than 70%, less than 65%, less than 60%, less than 55%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30% or less than 25% by weight. In some embodiments, based on the total weight of the conductive layer, the proportion of the binder material and the conductive material in the conductive layer of the modified current collector is independently more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 55%, more than 60%, more than 65% or more than 70% by weight.
[0121] The thickness of the modified current collector in the electrode may affect the volume it occupies in the battery, the space available for the electrode active material in the electrode layer, and thus affect the capacity of the battery. In certain embodiments, the thickness of the modified current collector is about 5 μm to about 70 μm, about 5 μm to about 60 μm, about 5 μm to about 50 μm, about 5 μm to about 40 μm, about 5 μm to about 30 μm, about 5 μm to about 20 μm, about 10 μm to about 70 μm, about 10 μm to about 60 μm, about 10 μm to about 50 μm, about 10 μm to about 40 μm, about 10 μm to about 30 μm, about 20 μm to about 70 μm, about 20 μm to about 60 μm, about 20 μm to about 50 μm, about 20 μm to about 40 μm, about 30 μm to about 70 μm, or about 30 μm to about 50 μm.
[0122] In some embodiments, the thickness of the modified current collector is less than 70 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, less than 25 μm, less than 20 μm, less than 15 μm or less than 10 μm. In some embodiments, the thickness of the modified current collector is greater than 5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 25 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm or greater than 60 μm.
[0123] The thickness of the substrate in the modified current collector may affect the volume occupied by it in the modified current collector and / or the electrode. This may affect the space available for the conductive material and the binder material in the conductive layer and / or the electrode active material in the electrode layer. Therefore, the conductivity of the battery system, the adhesion ability of the conductive layer to the substrate, and the capacity of the battery may be affected. In some embodiments, the thickness of the substrate in the modified current collector is about 5 μm to about 50 μm, about 5 μm to about 40 μm, about 5 μm to about 30 μm, about 5 μm to about 20 μm, about 5 μm to about 10 μm, about 10 μm to about 50 μm, about 10 μm to about 40 μm, about 10 μm to about 30 μm, about 15 μm to about 50 μm, about 15 μm to about 40 μm, about 15 μm to about 30 μm, about 20 μm to about 50 μm, or about 20 μm to about 40 μm.
[0124] In some embodiments, the thickness of the substrate in the modified current collector is less than 50 μm, less than 45 μm, less than 40 μm, less than 35 μm, less than 30 μm, less than 25 μm, less than 20 μm, less than 15 μm, less than 10 μm or less than 5 μm. In some embodiments, the thickness of the substrate in the modified current collector is greater than 5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 25 μm, greater than 30 μm, greater than 35 μm, greater than 40 μm or greater than 45 μm.
[0125] Similarly, the thickness of the conductive layer affects the total volume of the modified current collector, thereby affecting the capacity of the final battery. In some embodiments, the thickness of the conductive layer in the modified current collector is about 0.1 μm to about 20 μm, about 0.1 μm to about 15 μm, about 0.1 μm to about 10 μm, about 0.1 μm to about 5 μm, about 1 μm to about 20 μm, about 1 μm to about 15 μm, about 1 μm to about 10 μm, about 1 μm to about 5 μm, about 5 μm to about 20 μm, about 5 μm to about 15 μm, or about 5 μm to about 10 μm.
[0126] In some embodiments, the thickness of the conductive layer in the modified current collector is less than 20 μm, less than 18 μm, less than 16 μm, less than 14 μm, less than 12 μm, less than 10 μm, less than 8 μm, less than 6 μm, less than 4 μm, less than 2 μm or less than 1 μm. In some embodiments, the thickness of the conductive layer in the modified current collector is greater than 0.1 μm, greater than 0.5 μm, greater than 1 μm, greater than 2 μm, greater than 4 μm, greater than 6 μm, greater than 8 μm, greater than 10 μm, greater than 12 μm, greater than 14 μm, greater than 16 μm or greater than 18 μm.
[0127] As described above, in some embodiments, the conductive layer in the modified current collector of the present invention is produced by a conductive paste. In some embodiments, the conductive paste comprises a conductive material, a binder material and a solvent. In some embodiments, the solvent in the conductive paste is a polar solvent.
[0128] Some non-limiting examples of polar solvents include water, alcohol, lower aliphatic ketones, lower acetic acid alkyl esters and combinations thereof. Some non-limiting examples of alcohol include C1-C4 alcohols, such as methanol, ethanol, isopropanol, n-propanol, tert-butyl alcohol, n-butyl alcohol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, ethylene glycol, propylene glycol, glycerine and combinations thereof. Some non-limiting examples of lower aliphatic ketones include acetone, dimethyl ketone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK) and combinations thereof. Some non-limiting examples of lower acetic acid alkyl esters include ethyl acetate (EA), isopropyl acetate, propyl acetate, butyl acetate (BA) and combinations thereof. In some embodiments, the solvent of the conductive paste is water. In other embodiments, the solvent of the conductive paste does not include water.
[0129] In some embodiments, the solvent of the conductive paste may be a mixture of water and one or more polar compounds. In certain embodiments, the weight ratio of water to the one or more polar compounds is about 99:1 to about 1:99, about 90:10 to about 1:99, about 80:20 to about 1:99, about 70:30 to about 1:99, about 60:40 to about 1:99, about 50:50 to about 1:99, about 99:1 to about 50:50, about 99:1 to about 40:60, about 99:1 to about 30:70, about 99:1 to about 20:80, or about 99:1 to about 10:90. In certain embodiments, the solvent of the conductive paste may be in the form of an emulsion or a colloid.
[0130] Since various monomer units in the binder material contain polar substituents, it is advantageous to use a polar solvent and will therefore dissolve in the polar solvent to form a well-dispersed slurry. Among them, ethanol and isopropanol are particularly suitable as polar solvents due to their relatively low cost, toxicity and impact on the environment.
[0131] In some embodiments, the polar solvent may further comprise a secondary component. Some non-limiting examples of secondary components include tetrahydrofuran (THF), acetonitrile, dimethyl sulfoxide, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and combinations thereof.
[0132] In some embodiments, the solids content of the conductive paste is about 5% to about 25%, about 10% to about 25%, about 15% to about 25%, about 5% to about 20%, about 10% to about 20%, about 15% to about 20%, about 5% to about 15%, or about 10% to about 15% by weight, based on the total weight of the conductive paste.
[0133] In some embodiments, the solid content of the conductive paste is less than 25%, less than 23%, less than 20%, less than 19%, less than 18%, less than 17%, less than 16%, less than 15%, less than 14%, less than 13%, less than 10%, less than 8%, or less than 6% by weight, based on the total weight of the conductive paste. In some embodiments, the solid content of the conductive paste is more than 5%, more than 6%, more than 7%, more than 8%, more than 9%, more than 10%, more than 11%, more than 12%, more than 13%, more than 14%, more than 15%, more than 16%, more than 17%, more than 18%, more than 19%, more than 20%, or more than 22% by weight, based on the total weight of the conductive paste.
[0134] There is no particular limitation on the method used in producing the conductive paste, but all components of the paste (e.g., conductive material, binder material, aqueous solvent) should be uniformly mixed (e.g., by using a homogenizer) to form a homogenized paste. In some embodiments, all components of the conductive paste are added to the homogenizer at one time. In other embodiments, the components of the conductive paste can be added to the homogenizer in one or more batches, and each batch can contain one or more components. An advantage of the present invention is that the conductive paste is easy to homogenize without the need for surfactants and dispersants.
[0135] Any homogenizer that can reduce or eliminate particle aggregation and / or promote uniform distribution of the components of the conductive paste can be used in the present invention. In some embodiments, the homogenizer is a planetary stirring mixer, a stirring mixer, a mixer or an ultrasonic generator. There is no particular limitation on the stirring speed and time used, but it should be sufficient to make the conductive material and the binder material well dispersed in the solvent to ensure that when the conductive paste is applied to the substrate, the coating is homogeneous.
[0136] In addition, there is no particular limitation on the temperature at which the conductive paste is homogenized, but it should not be too high to cause boiling of the solvent, but at the same time be high enough to ensure that the paste is not too viscous to affect processability, and the binder material can be easily dissolved in the paste. In some embodiments, the temperature at which the conductive paste is homogenized is room temperature or a temperature of about 20° C. to about 95° C.
[0137] In some embodiments, the temperature at which the conductive paste is homogenized is less than 95° C., less than 85° C., less than 75° C., less than 65° C., less than 55° C., less than 50° C., less than 45° C., less than 40° C., less than 35° C., less than 30° C., or less than 25° C. In some embodiments, the temperature at which the conductive paste is homogenized is greater than 20° C., greater than 25° C., greater than 30° C., greater than 35° C., greater than 40° C., greater than 45° C., greater than 50° C., greater than 55° C., greater than 60° C., greater than 65° C., greater than 70° C., or greater than 75° C.
[0138] In some embodiments, after the conductive slurry is homogenized, the slurry can be coated on one or both sides of the substrate to form a conductive layer film. There are no particular restrictions on the equipment and conditions used for coating the conductive slurry, but the formed coating should be uniform, flat and smooth. In certain embodiments, the coating process can be performed using a blade coater, a slot extrusion coater, a transfer coater, a spray coater, a roll coater, a gravure coater, a dip coater or a curtain coater.
[0139] In some embodiments, after the conductive slurry is applied to the substrate, the coating is dried to form the modified current collector of the present invention. Any device that can dry the coating to fix the resulting conductive layer to the substrate can be used in the present invention. Some non-limiting examples of the drying equipment include vacuum drying ovens, batch drying ovens, conveyor belt drying ovens, and microwave drying ovens.
[0140] There is no particular limitation on the conditions used for drying, but the drying conditions should be sufficient to ensure that the conductive layer is firmly attached to the substrate. However, drying the conductive layer at a temperature above 100°C may cause undesirable deformation of the resulting modified current collector, thereby affecting the performance of any electrode prepared therefrom. The drying temperature should be optimized based on other drying conditions (e.g., drying time) to ensure that the solvent is fully removed from the conductive layer.
[0141] In some embodiments, the modified current collector is mechanically compressed after drying to increase the density of the conductive layer, and then when the electrode layer is formed on the modified current collector, a finished electrode can be formed. In other embodiments, the modified current collector is not compressed.
[0142] The electrode can then be prepared by forming an electrode layer on the modified current collector of the present invention. There is no particular restriction on the composition of the electrode layer, and any composition known in the art is applicable to the present invention, as long as any battery containing the electrode can achieve excellent electrochemical performance. The composition of this electrode layer depends on the type of battery produced, and whether the electrode layer is used for the anode or cathode of the battery. In some embodiments, the type of battery can be a primary battery or a secondary battery. Some non-limiting examples of battery types include alkaline batteries, aluminum-air batteries, lithium batteries, lithium-air batteries, magnesium batteries, silver oxide batteries, zinc-air batteries, aluminum ion batteries, lead-acid batteries, lithium ion batteries, magnesium ion batteries, potassium ion batteries, sodium ion batteries, sodium-air batteries, silicon-air batteries, zinc ion batteries, and sodium-sulfur batteries. In addition, depending on the state of the electrolyte used (i.e., liquid or solid), the battery can be divided into a conventional battery (when a liquid electrolyte is used) or a solid-state battery (when a solid electrolyte is used).
[0143] In some embodiments, the electrode layer comprises an electrode active material and a binder. In certain embodiments, the electrode layer further comprises a conductive agent. The electrode active material in the electrode layer can be a cathode active material or an anode active material. When the electrode layer comprises a cathode active material, the electrode layer is a cathode electrode layer. When the electrode layer comprises an anode active material, the electrode layer is an anode electrode layer.
[0144] In some embodiments, the electrode active material is a cathode active material. In some embodiments, the cathode active material is selected from LiCoO2, LiNiO2, LiNi 1-x M x O2、LiNi x Mn y O2、LiCo x Ni y O2、Li 1+z Ni x Mn y Co 1-x-y O2、LiNi x Co y Al zO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4 and a combination thereof, wherein each x is independently 0.1 to 0.9; each y is independently 0 to 0.9; each z is independently 0 to 0.4; and M is selected from the group consisting of Co, Mn, Al, Fe, Ti, Ga, Mg and a combination thereof. In certain embodiments, each x in the above formula is independently selected from 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875 and 0.9; each y in the above formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0 .2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875 and 0.9; each z in the above formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375 and 0.4. In some embodiments, each x, y and z in the above formula independently has an interval of 0.01.
[0145] In certain embodiments, the cathode active material is selected from LiNi x Mn y O2、Li 1+z Ni x Mn y Co 1-x-y O2(NMC), LiNi x Co y Al z O2(NCA), LiCo x Ni yO2 and combinations thereof, wherein each x is independently 0.4 to 0.6; each y is independently 0.2 to 0.4; and each z is independently 0 to 0.1. In other embodiments, the cathode active material is not LiCoO2, LiNiO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2 or LiFePO4. In further embodiments, the cathode active material is not LiNi x Mn y O2、Li 1+z Ni x Mn y Co 1-x-y O2、LiNi x Co y Al z O2 or LiCo x Ni y O2, wherein each x is independently 0.1 to 0.9; each y is independently 0 to 0.45; and each z is independently 0 to 0.2. In certain embodiments, the cathode active material is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2; wherein -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1, and a+b+c≤1. In some embodiments, the cathode active material has the general formula Li 1+ x Ni a Mn b Co c Al (1-a-b-c)O2, where 0.33 ≤ a ≤ 0.92, 0.33 ≤ a ≤ 0.9, 0.33 ≤ a ≤ 0.8, 0.4 ≤ a ≥ 0.92, 0.4 ≤ a ≤ 0.9, 0.4 ≤ a ≤ 0.8, 0.5 ≤ a ≤ 0.92, 0.5 ≤ a ≤ 0.9, 0.5 ≤ a ≤ 0.8, 0.6 ≤ a ≤ 0.92 or 0.6 ≤ a ≤ 0.9; 0 ≤ b ≤ 0.5, 0 ≤ b ≤ 0.4, 0 ≤ b ≤ 0.3, 0 ≤ b ≤ 0.2, 0.1 ≤ b ≤ 0.5, 0.1 ≤ b ≤ 0.4, 0.1 ≤ b ≤ 0.3, 0.1 ≤ b ≤ 0.2, 0.2 ≤ b ≤ 0.5, 0.2 ≤ b ≤ 0.4 or 0.2 ≤ b ≤ 0.3; 0 ≤ c ≤ 0.5, 0 ≤ c ≤ 0.4, 0 ≤ c ≤ 0.3, 0.1 ≤ c ≤ 0.5, 0.1 ≤ c ≤ 0.4, 0.1 ≤ c ≤ 0.3, 0.1 ≤ c ≤ 0.2, 0.2 ≤ c ≤ 0.5, 0.2 ≤ c ≤ 0.4 or 0.2 ≤ c ≤ 0.3. In some embodiments, the cathode active material has the general formula LiMPO4, where M is selected from the group consisting of Fe, Co, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge or combinations thereof.
[0146] In some embodiments, the cathode active material is selected from the group consisting of LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, LiMnFePO4, LiMn x Fe (1-x) PO4 and combinations thereof; where 0 < x < 1. In some embodiments, the cathode active material is LiNi x Mn y O4; where 0.1 ≤ x ≤ 0.9 and 0 ≤ y ≤ 2. In certain embodiments, the cathode active material is xLi2MnO3·(1 - x)LiMO2, where M is selected from the group consisting of Ni, Co, Mn and combinations thereof; and where 0 < x < 1. In some embodiments, the cathode active material is Li3V2(PO4)3 or LiVPO4F. In certain embodiments, the cathode active material has the general formula Li2MSiO4, where M is selected from the group consisting of Fe, Co, Mn, Ni and combinations thereof.
[0147] In certain embodiments, the cathode active material is doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge and combinations thereof. In some embodiments, the cathode active material is not doped with Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si or Ge. In certain embodiments, the cathode active material is not doped with Al, Sn or Zr.
[0148] In some embodiments, the cathode active material is LiNi 0.33 Mn 0.33 Co 0.33 O2(NMC333),LiNi 0.4 Mn 0.4 Co 0.2 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2(NMC532),LiNi 0.6 Mn 0.2 Co 0.2 O2(NMC622),LiNi 0.7 Mn 0.15 Co 0.15 O2、LiNi 0.7 Mn 0.1 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811), LiNi 0.92 Mn 0.04 Co 0.04 O2、LiNi 0.85 Mn 0.075 Co 0.075 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.88 Co 0.1 Al 0.02 O2, LiNiO2 (LNO) or a combination thereof.
[0149] In other embodiments, the cathode active material is not LiCOO2, LiNio2, LiMnO2, LiMn2O4 or Li2MnO3. In further embodiments, the cathode active material is not LiNi 0.33 Mn 0.33 Co 0.33 O2、LiNi 0.4 Mn 0.4 Co 0.2 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.7 Mn 0.15 Co 0.15 O2、LiNi0.7 Mn 0.1 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2、LiNi 0.92 Mn 0.04 Co 0.04 O2、LiNi 0.85 Mn 0.075 Co 0.075 O2、LiNi 0.8 Co 0.15 Al 0.05 O2 or LiNi 0.88 Co 0.1 Al 0.02 O2.
[0150] In certain embodiments, the cathode active material comprises or is itself a core-shell composite material having a core and shell structure, wherein the core comprises a selected from Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12 , LiV2O5, LiTiS2, LiMoS2, LiCo a Ni b O2、LiMn a Ni b O2 and a combination thereof; wherein -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1 and a+b+c≤1. In some embodiments, the shell further comprises a lithium transition metal oxide. In certain embodiments, the lithium transition metal oxide of the shell is selected from the group of lithium transition metal oxides for the core described above. In other embodiments, the shell comprises a transition metal oxide. In certain embodiments, the transition metal oxide of the shell is selected from the group consisting of Fe2O3, MnO2, Al2O3, MgO, ZnO, TiO2, La2O3, CeO2, SnO2, ZrO2, RuO2 and a combination thereof. In certain embodiments, the shell comprises a lithium transition metal oxide and a transition metal oxide.
[0151] In some embodiments, the core and shell each independently comprise two or more lithium transition metal oxides. In some embodiments, one of the core or shell comprises only one lithium transition metal oxide, and the other comprises two or more lithium transition metal oxides. The lithium transition metal oxides in the core and shell may be the same, different or partially different. In some embodiments, two or more lithium transition metal oxides are uniformly distributed on the core. In some embodiments, two or more lithium transition metal oxides are unevenly distributed on the core.
[0152] In some embodiments, each of the metal oxides in the core and shell is independently doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the cathode active material is not a core-shell composite.
[0153] In some embodiments, the electrode active material is a cathode active material for a sodium ion battery. In some embodiments, the cathode active material for a sodium ion battery is a material satisfying the formula Na x M y A z Prussian blue type sodium compound, wherein M is one or more metals and A is one or more anions comprising one or more of O, P, N, C, H or halogen. In certain embodiments, the cathode active material for the sodium ion battery is a sodium analog of the above cathode active material, wherein lithium is replaced by sodium. In some embodiments, the cathode active material for the sodium ion battery is selected from the group consisting of NaCoO2, NaFeO2, NaNiO2, NaCrO2, NaVO2 and NaTiO2, NaFePO4, Na3V2(PO4)3, Na3V2(PO4)2F3, NMC-type mixed oxides and combinations thereof. In some embodiments, the cathode active material for the sodium ion battery is an organic material, such as disodium naphthalene diimide, doped quinones, pteridine derivatives, polyimides, polyamic acids or combinations thereof.
[0154] In some embodiments, the cathode active material for a sodium ion battery comprises or is itself a core-shell composite material having a core and shell structure. In some embodiments, the cathode active material for a sodium ion battery is doped with a dopant. The same dopants listed above for the cathode active material for a lithium ion battery can be used to dope the cathode active material for a sodium ion battery.
[0155] In some embodiments, the average diameter of the cathode active material particles is about 0.1 μm to about 100 μm, about 0.1 μm to about 50 μm, about 0.5 μm to about 50 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 20 μm, about 1 μm to about 20 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 5 μm to about 50 μm, about 10 μm to about 50 μm, about 20 μm to about 50 μm, or about 50 μm to about 100 μm.
[0156] In some embodiments, the average diameter of the cathode active material particles is less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, less than 20 μm, less than 15 μm, less than 10 μm, less than 7.5 μm, less than 5 μm, less than 2.5 μm, less than 1 μm, less than 0.75 μm, or less than 0.5 μm. In some embodiments, the average diameter of the cathode active material particles is greater than 0.1 μm, greater than 0.25 μm, greater than 0.5 μm, greater than 0.75 μm, greater than 1 μm, greater than 2.5 μm, greater than 5 μm, greater than 7.5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 30 μm, greater than 40 μm, or greater than 50 μm.
[0157] In some embodiments, the electrode active material is an anode active material. In some embodiments, the anode active material is selected from natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particles, SnO2, SnO, Li4Ti μ O 12 The group consisting of Si particles, Si particles, Si-C composite particles and combinations thereof.
[0158] In certain embodiments, the anode active material is doped with a metal element or a non-metal element. In some embodiments, the metal element is selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, and combinations thereof. In some embodiments, the non-metal element is B, Si, Ge, N, P, F, S, Cl, I, Se, or a combination thereof.
[0159] In some embodiments, the anode active material comprises or is itself a core-shell composite material having a core and shell structure, wherein the core and the shell are each independently selected from natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesophase carbon microbeads (MCMB), Sn particles, SnO2, SnO, Li4Ti5O 12 The group consisting of Si particles, Si particles, Si-C composite particles and combinations thereof.
[0160] In certain embodiments, the anode active material in the form of a core-shell composite material comprises a core containing a carbonaceous material and a shell coated on the carbonaceous material core. In some embodiments, the carbonaceous material is selected from the group consisting of soft carbon, hard carbon, natural graphite particles, synthetic graphite particles, mesocarbon microbeads, Kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fibers, and combinations thereof. In certain embodiments, the shell is selected from the group consisting of natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particles, SnO2, SnO, Li4Ti s O 12 particles, Si particles, Si-C composite particles, and combinations thereof.
[0161] In certain embodiments, the anode active material is not doped with a metal element or a non-metal element. In some embodiments, the anode active material is not doped with Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, B, Si, Ge, N, P, F, S, Cl, I, or Se.
[0162] In some embodiments, the electrode active material is an anode active material for a sodium-ion battery. Many embodiments of anode active materials for lithium-ion batteries are also suitable for use as anode active materials for sodium-ion batteries. However, graphite is not preferred because the pores in the material are too small to accommodate sodium ions. Li4Ti5O 12 particles are also not preferred as anode active materials for sodium-ion batteries because the presence of lithium will affect the reaction mechanism of sodium-ion batteries.
[0163] In some embodiments, the anode active material for a sodium-ion battery is selected from the group consisting of hard carbon, soft carbon, tin oxides (such as SnO2 and SnO), sodium titanates (such as NaTi2(PO4)3 and Na2Ti3O7), SnS2, NbS2, SbO x , where 0 < x ≤ 2, Sn-P compounds and complexes, sodium alloys, and combinations thereof. In some embodiments, the anode active material for a sodium-ion battery is a Prussian blue-type sodium compound that satisfies the formula Na x M y A z where M is one or more metals and A is one or more anions containing one or more of O, P, N, C, H, or a halogen. In some embodiments, the cathode active material for a sodium-ion battery is an organic material, such as disodium naphthalenediimide, doped quinones, pteridine derivatives, polyimides, polyamic acids, or combinations thereof.
[0164] In some embodiments, the anode active material for a sodium ion battery comprises or is itself a core-shell composite material having a core and shell structure. In some embodiments, the anode active material for a sodium ion battery is doped with one or more elements selected from the group consisting of Sb, Sn, P, S, B, Al, Ga, In, Ge, Pb, As, Bi, Ti, Mo, Se, Te, Co, and combinations thereof.
[0165] The modified current collector of the present invention is particularly suitable for electrodes formed using water-based electrode slurries and comprising electrode layers containing nickel-containing cathode active materials. This slurry is essentially alkaline, so it will corrode conventional current collectors (the most common being aluminum foil). However, when an alkaline water-based cathode slurry is applied to the modified current collector of the present invention to form a cathode, the conductive layer in the modified current collector will form a physical barrier to prevent the conventional current collector (i.e., the substrate of the modified current collector) from contacting the slurry. Therefore, corrosion of the substrate is prevented. Nevertheless, the modified current collector of the present invention is suitable for electrodes comprising any suitable electrode active material (both cathode active material and anode active material), any type of battery, and any method of forming an electrode layer on the modified current collector.
[0166] In some embodiments, the electrode slurry contains a solvent in addition to various electrode components that form the electrode layer, such as electrode active materials, binders, and conductive agents. In some embodiments, the solvent of the electrode slurry is an aqueous solvent. In some embodiments, the aqueous solvent is water. In certain embodiments, the aqueous solvent in the conductive slurry further contains a secondary component other than water. In some embodiments, the volume ratio of water to the secondary component is about 51:49 to about 99:1.
[0167] Any water miscible or volatile solvent, including all minor components in the solvent of the above-mentioned conductive paste, can be used as a minor component in the aqueous solvent of the electrode slurry. When the aqueous solvent of the electrode slurry contains minor components other than water, the minor components may be the same as the minor components in the solvent of the conductive paste, or they may be different or partially different. Some non-limiting examples of minor components include alcohols, lower aliphatic ketones, lower alkyl acetates and combinations thereof. Adding minor components may improve the processability of the electrode slurry.
[0168] There is no particular restriction on the binder used in the electrode layer, but the binder should have the desired properties as a binder. For example, it is preferred that the binder can be well dispersed in the electrode slurry to form a uniform, smooth coating. When the electrode slurry containing the binder is coated on the surface of the modified current collector, the electrode slurry should not dissolve the conductive layer of the modified current collector. In some embodiments, more than one binder can be used in the electrode layer, as long as they do not dissolve the conductive layer of the modified current collector. In some embodiments, the binder is water-soluble.
[0169] In some embodiments, the binder in the electrode layer comprises a polymer. In some embodiments, the binder polymer in the electrode layer is a copolymer. In other embodiments, the binder polymer in the electrode layer is a homopolymer.
[0170] In certain embodiments, the binder in the electrode layer comprises styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylonitrile (PAN), polyacrylamide (PAM), acrylic acid-acrylonitrile-acrylamide copolymer, latex, alginate, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polystyrene, polyvinyl alcohol (PVA), polyvinyl acetate, polyisoprene, polyaniline, polyethylene, polyimide, polyurethane, polyvinyl butyral, polyvinyl pyrrolidone (PVP), gelatin, chitosan, starch, agar, xanthan gum, gum arabic, gellan gum, guar gum, karaya gum, tara gum, tragacanth gum, casein, amylose, pectin, PEDOT:PSS, carrageenan, or a combination thereof. In certain embodiments, the alginate comprises a cation selected from the group consisting of Na, Li, K, Ca, NH4, Mg, Al, and a combination thereof. In certain embodiments, the binder in the electrode layer does not include styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, polyacrylamide, acrylic acid-acrylonitrile-acrylamide copolymer, latex, alginate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, polystyrene, polyvinyl alcohol, polyvinyl acetate, polyisoprene, polyaniline, polyethylene, polyimide, polyurethane, polyvinyl butyral, polyvinyl pyrrolidone, gelatin, chitosan, starch, agar, xanthan gum, gum arabic, gellan gum, guar gum, karaya gum, tara gum, tragacanth gum, casein, amylose, pectin, PEDOT:PSS or carrageenan. In certain embodiments, the binder in the electrode layer does not include fluoropolymers such as PVDF, PVDF-HFP or PTFE.
[0171] In some embodiments, the binder in the electrode layer includes one or more functional groups containing halogen, O, N, S or a combination thereof. Some non-limiting examples of suitable functional groups include alkoxy, aryloxy, nitro, sulfhydryl, alkylthio, imines, cyano, amide, amino (primary amine, secondary amine or tertiary amine), carboxyl, epoxy, ketone, aldehyde, ester, hydroxyl, halogen (fluorine, chlorine, bromine or iodine) and a combination thereof. In some embodiments, the functional group is or includes carboxylic acid (i.e. -COOH), carboxylate, sulfonic acid, sulfonate, sulfuric acid, sulfate, phosphonic acid, phosphonate, phosphoric acid, phosphate, nitric acid, nitrate, amide, hydroxyl, nitrile, ester, epoxy or -NH2.
[0172] In certain embodiments, the binder in the electrode layer comprises a copolymer having the components described below, which contains three structural units, structural units (i), (ii) and (iii). Structural units (i) and (ii) are derived from monomers containing hydrophilic functional groups, while structural unit (iii) is derived from monomers containing hydrophobic functional groups. When the ratio of each of the various structural units of the copolymer in the binder falls within the following range, the combination of the hydrophilic functional groups and the hydrophobic functional groups in the copolymer is optimal. The hydrophilic functional groups present in the binder enable the copolymer to be well dispersed in an aqueous solvent and ensure that each electrode component can be connected together. On the other hand, the hydrophobic functional groups present in the binder help balance the hydrophilic functional groups and ensure that the binder will not self-aggregate due to the attraction between the hydrophilic functional groups of the different polymer chains of the binder. This further allows the electrode slurry to reach an optimal viscosity and dispersion, so that the electrode slurry can be easily handled and processed. Combined with hydrophilic and hydrophobic effects, this means that the various electrode components can be well combined while still remaining dispersed in a solvent of a water-based electrode slurry with high processability. The electrode layer produced using this slurry will be smooth and uniform, and the battery containing this electrode will have excellent capacity and electrochemical performance.
[0173] In some embodiments, the binder in the electrode layer comprises a structural unit (i) derived from a monomer containing an acid group, wherein the acid group is selected from the group consisting of carboxylic acid, sulfonic acid, sulfuric acid, phosphonic acid, phosphoric acid, nitric acid and a combination thereof. The acids listed above also include their salts and derivatives. In some embodiments, the salt of the acid comprises an alkali metal cation. Examples of alkali metals that form alkali metal cations include lithium, sodium and potassium. In some embodiments, the salt of the acid comprises an ammonium cation.
[0174] In some embodiments, the carboxylic acid is acrylic acid, methacrylic acid, crotonic acid, 2-butyl crotonic acid, cinnamic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, 4,4-dimethylitaconic acid, or a combination thereof. In certain embodiments, the carboxylic acid is 2-ethylacrylic acid, isocrotonic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid , 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid or a combination thereof.
[0175] In some embodiments, the sulfonic acid is vinyl sulfonic acid, methyl vinyl sulfonic acid, allyl vinyl sulfonic acid, allyl sulfonic acid, methyl allyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl methacrylic acid, 2-methyl-2-propylene-1-sulfonic acid, 2-acrylamido-2-methyl-1-propane sulfonic acid, 3-allyloxy-2-hydroxy-1-propane sulfonic acid, or a combination thereof.
[0176] In some embodiments, the sulfuric acid is allyl hydrogen sulfate, vinyl hydrogen sulfate, 4-allylphenol sulfate, or a combination thereof.
[0177] In some embodiments, the phosphonic acid is phosphinoxyethyl acrylate, phosphinoxyethyl methacrylate, vinylphosphonic acid, allylphosphonic acid, 3-butenylphosphonic acid, styrenephosphonic acid, vinylbenzylphosphonic acid, (2-chloro-2-phenyl-vinyl)-phosphonic acid, acrylamidoalkylphosphonic acid, methacrylamidoalkylphosphonic acid, acrylamidoalkyldiphosphonic acid, acrylphosphonic acid, 2-methacryloyloxyethylphosphonic acid, bis(2-methacryloyloxyethyl)phosphonic acid, ethylene 2-methacryloyloxyethylphosphonic acid, ethyl-methacryloyloxyethylphosphonic acid, or a combination thereof.
[0178] In some embodiments, the phosphoric acid is mono(2-acryloyloxyethyl)phosphate, mono(2-methacryloyloxyethyl)phosphate, diphenyl(2-acryloyloxyethyl)phosphate, diphenyl(2-methacryloyloxyethyl)phosphate, phenyl(2-acryloyloxyethyl)phosphate, phosphoethyl methacrylate, 3-chloro-2-phosphopropyl methacrylate, phosphooxypoly(ethylene glycol)monomethacrylate, phosphooxypoly(propylene glycol)methacrylate, (meth)acryloyloxyethylphosphonic acid Ester, (meth)acryloxypropyl phosphate, (meth)acryloxy-2-hydroxypropyl phosphate, (meth)acryloxy-3-hydroxypropyl phosphate, (meth)acryloxy-3-chloro-2-hydroxypropyl phosphate, allyl hydrogen phosphate, vinyl hydrogen phosphate, allyl hydrogen pyrophosphate, vinyl hydrogen pyrophosphate, allyl hydrogen tripolyphosphate, vinyl hydrogen tripolyphosphate, allyl hydrogen tetrapolyphosphate, vinyl hydrogen tetrapolyphosphate, allyl hydrogen trimetaphosphate, vinyl hydrogen trimetaphosphate, isopentenyl phosphate, isopentenyl pyrophosphate, or a combination thereof.
[0179] In some embodiments, the nitric acid is allyl hydrogen nitrate, vinyl hydrogen nitrate, or a combination thereof.
[0180] In some embodiments, based on the total moles of the monomer units in the copolymer, the proportion of structural unit (i) in the binder is about 15% to about 95%, about 15% to about 85%, about 15% to about 75%, about 15% to about 65%, about 15% to about 55%, about 20% to about 95%, about 20% to about 90%, about 20% to about 80%, about 20% to about 70%, about 20% to about 60%, about 20% to about 50%, about 25% to about 95%, about 25% to about 85%, about 25% to about 75%, about 25% to about 65%, about 25% to about 55%, about 30% to about 9 ... 0% to about 85%, about 30% to about 75%, about 30% to about 65%, about 35% to about 95%, about 35% to about 85%, about 35% to about 75%, about 35% to about 65%, about 40% to about 95%, about 40% to about 85%, about 40% to about 75%, about 40% to about 65%, about 45% to about 95%, about 45% to about 85%, about 45% to about 75%, about 50% to about 95%, about 50% to about 85%, about 50% to about 75%, about 55% to about 95%, about 55% to about 85%, about 55% to about 75%, about 60% to about 95%, or about 60% to about 85%.
[0181] In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (i) in the binder is less than 95%, less than 85%, less than 75%, less than 65%, less than 55%, less than 45%, less than 35% or less than 25% by mole. In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (i) in the binder is more than 15%, more than 25%, more than 35%, more than 45%, more than 55%, more than 65%, more than 75% or more than 85% by mole.
[0182] In some embodiments, the binder in the electrode layer further comprises a structural unit (ii) derived from a monomer selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, and a combination thereof.
[0183] In some embodiments, the monomer containing an amide group is acrylamide, methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, N-n-propyl methacrylamide, N-isopropyl methacrylamide, isopropyl acrylamide, N-n-butyl methacrylamide, N-isobutyl methacrylamide, N,N-dimethyl acrylamide, N,N-dimethyl methacrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-hydroxymethyl methacrylamide, N-(methoxymethyl) methacrylamide, N-(ethoxymethyl) methacrylamide , N-(propyloxymethyl)methacrylamide, N-(butoxymethyl)methacrylamide, N,N-dimethylmethacrylamide, N,N-(dimethylaminopropyl)methacrylamide, NN-(dimethylaminoethyl)methacrylamide, N,N-(dihydroxymethyl)methacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryl morpholine, N-(hydroxy)methacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, N,N′-methylene-bis-acrylamide (MBA), N-hydroxymethylacrylamide, or a combination thereof.
[0184] In some embodiments, the monomer containing a hydroxyl group is a monomer containing a hydroxyl group and containing C1-C 20 Alkyl or C5-C 20 In some embodiments, the monomer containing a hydroxyl group is 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 5-hydroxypentyl acrylate, 6-hydroxyhexyl methacrylate, 1,4-cyclohexanedimethanol monoacrylate, 1,4-cyclohexanedimethanol monomethacrylate, 3-chloro-2-hydroxypropyl methacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, allyl alcohol, or a combination thereof.
[0185] In some embodiments, the proportion of structural unit (ii) in the binder is about 5% to about 50%, about 5% to about 45%, about 5% to about 40%, about 5% to about 35%, about 5% to about 30%, about 5% to about 25%, about 10% to about 50%, about 10% to about 45%, about 10% to about 40%, about 10% to about 35%, about 10% to about 30%, about 15% to about 50%, about 15% to about 45%, about 15% to about 40%, about 20% to about 50%, about 20% to about 45%, about 20% to about 40%, or about 25% to about 50% by mole, based on the total moles of the monomer units in the copolymer.
[0186] In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (ii) in the binder is less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, or less than 15% by mole. In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (ii) in the binder is more than 5%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35% or more than 40% by mole.
[0187] In some embodiments, the binder in the electrode layer further comprises a structural unit (iii) derived from a monomer selected from the group consisting of a nitrile group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, and a combination thereof.
[0188] In some embodiments, the monomer containing nitrile groups is or comprises α, β-ethylenically unsaturated nitrile monomers. In some embodiments, the monomer containing nitrile groups is acrylonitrile, α-halogenated acrylonitrile, α-alkyl acrylonitrile or a combination thereof. In some embodiments, the monomer containing nitrile groups is α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide or a combination thereof.
[0189] In some embodiments, the ester group-containing monomer is an acrylic acid C1-C 20 Alkyl esters, methacrylate C1-C 20 In some embodiments, the monomer containing the ester group is methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 3,3,5-trimethylhexyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, octadecyl acrylate, cyclohexyl acrylate, phenyl acrylate, methoxymethyl acrylate, methoxyethyl acrylate, ethoxymethyl acrylate, ethoxyethyl acrylate, perfluorooctyl acrylate, octadecyl acrylate or a combination thereof.
[0190] In some embodiments, the epoxy group-containing monomer is vinyl glycidyl ether, allyl glycidyl ether, allyl 2,3-epoxypropyl ether, butenyl glycidyl ether, butadiene monoepoxide, chloroprene monoepoxide, 3,4-epoxy-1-butene, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexane, 1,2-epoxy-4-vinylcyclohexane, 3,4-epoxycyclohexylethylene, epoxy-4-vinylcyclohexene, 1,2-epoxy-5,9-cyclododecadiene, or a combination thereof.
[0191] In some embodiments, based on the total moles of the monomer units in the copolymer, the proportion of the structural unit (iii) in the binder is about 5% to about 80%, about 5% to about 70%, about 5% to about 60%, about 5% to about 50%, about 5% to about 40%, about 5% to about 30%, about 10% to about 80%, about 10% to about 70%, about 10% to about 60%, about 10% to about 50%, about 10% to about 40%, about 15% to about 80%, about 15% to about 70%, about 15% to about 60%, about 15% to about 50%, about 15% to about 40%, , about 20% to about 80%, about 20% to about 70%, about 20% to about 60%, about 20% to about 50%, about 25% to about 80%, about 25% to about 70%, about 25% to about 60%, about 25% to about 50%, about 30% to about 80%, about 30% to about 70%, about 30% to about 60%, about 35% to about 80%, about 35% to about 70%, about 35% to about 60%, about 40% to about 80%, about 40% to about 70%, about 45% to about 80%, about 45% to about 70%, about 50% to about 80% or about 50% to about 70%.
[0192] In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (iii) in the binder is less than 80%, less than 70%, less than 60%, less than 50%, less than 40%, less than 30%, less than 20% or less than 15% by mole. In some embodiments, based on the total moles of monomer units in the copolymer, the proportion of structural unit (iii) in the binder is more than 5%, more than 15%, more than 25%, more than 35%, more than 45%, more than 55% or more than 60% by mole.
[0193] In some embodiments, the electrode layer further comprises a conductive agent. The presence of the conductive agent enhances the electrical conductivity of the electrode layer in the electrode. Therefore, it may be advantageous for the electrode layer to comprise a conductive agent. Any suitable material may be used as the conductive agent. Any embodiment of the conductive material of the conductive layer of the modified current collector of the present invention is also suitable for use as the conductive agent in the electrode layer. In other embodiments, the conductive agent is not a conductive material in the conductive layer of the modified current collector. The conductive agent for the electrode layer and the conductive material for the conductive layer of the modified current collector may be the same, different or partially different.
[0194] In some embodiments, the conductive agent comprises a conductive polymer selected from the group consisting of polypyrrole, polyaniline, polyacetylene, polyphenylene sulfide (PPS), polyphenylene vinylene (PPV), poly(3,4-ethylenedioxythiophene) (PEDOT), polythiophene, and combinations thereof. In some embodiments, the conductive polymer plays two roles at the same time, not only as a conductive agent but also as a binder. In other embodiments, the conductive agent does not comprise a conductive polymer.
[0195] In some embodiments, the electrode active material in the electrode layer comprises about 60% to about 99%, about 70% to about 99%, about 75% to about 99%, about 80% to about 99%, about 85% to about 99%, about 90% to about 99%, about 60% to about 95%, about 65% to about 95%, about 70% to about 95%, about 75% to about 95%, about 80% to about 95%, about 85% to about 95%, about 60% to about 90%, about 65% to about 90%, about 70% to about 90%, about 75% to about 90%, about 80% to about 90%, about 60% to about 85%, about 65% to about 85%, about 70% to about 85%, about 75% to about 85%, about 60% to about 80%, about 65% to about 80%, or about 70% to about 80% by weight.
[0196] In some embodiments, based on the total weight of the electrode layer, the proportion of electrode active material in the electrode layer is less than 99%, less than 95%, less than 90%, less than 85%, less than 80%, less than 75%, less than 70%, or less than 65% by weight. In some embodiments, based on the total weight of the electrode layer, the proportion of electrode active material in the electrode layer is more than 60%, more than 65%, more than 70%, more than 75%, more than 80%, more than 85%, more than 90%, or more than 95% by weight.
[0197] In some embodiments, based on the total weight of the electrode layer, the proportion of the binder and the conductive agent in the electrode layer is independently about 1% to about 20%, about 2% to about 20%, about 3% to about 20%, about 4% to about 20%, about 5% to about 20%, about 6% to about 20%, about 7% to about 20%, about 8% to about 20%, about 9% to about 20%, about 10% to about 20%, about 15% to about 20%, about 1% to about 15% by weight. %, about 2% to about 15%, about 3% to about 15%, about 4% to about 15%, about 5% to about 15%, about 6% to about 15%, about 7% to about 15%, about 8% to about 15%, about 9% to about 15%, about 10% to about 15%, about 1% to about 10%, about 2% to about 10%, about 3% to about 10%, about 4% to about 10%, about 5% to about 10%, about 1% to about 5%, about 2% to about 5% or about 3% to about 5%.
[0198] In some embodiments, based on the total weight of the electrode layer, the proportion of the binder and the conductive agent in the electrode layer is independently less than 20%, less than 19%, less than 18%, less than 17%, less than 16%, less than 15%, less than 14%, less than 13%, less than 12%, less than 11%, less than 10%, less than 9%, less than 8%, less than 7% or less than 6%. In some embodiments, based on the total weight of the electrode layer, the proportion of the binder and the conductive agent in the electrode layer is independently more than 1%, more than 2%, more than 3%, more than 4%, more than 5%, more than 6%, more than 7%, more than 8%, more than 9%, more than 10%, more than 11%, more than 12%, more than 13%, more than 14% or more than 15%.
[0199] In some embodiments, the electrode layer of the electrode may further include other additives for enhancing electrode performance. In some embodiments, the additives may include surfactants, dispersants and flexibility enhancing additives, salts, ion conductive polymers and inorganic solid electrolytes.
[0200] In some embodiments, the solids content of the electrode slurry is about 40% to about 80%, about 40% to about 75%, about 40% to about 70%, about 40% to about 65%, about 40% to about 60%, about 40% to about 55%, about 45% to about 80%, about 45% to about 75%, about 45% to about 70%, about 45% to about 65%, about 45% to about 60%, about 50% to about 80%, about 50% to about 75%, about 50% to about 70%, about 50% to about 65%, about 55% to about 80%, about 55% to about 75%, about 55% to about 70%, about 60% to about 80%, about 60% to about 75%, about 65% to about 80%, about 65% to about 75%, or about 70% to about 80% by weight based on the total weight of the electrode slurry.
[0201] In some embodiments, the solid content of the electrode slurry is less than 80%, less than 75%, less than 70%, less than 65%, less than 60%, less than 55%, or less than 50% by weight based on the total weight of the electrode slurry. In some embodiments, the solid content of the electrode slurry is more than 40%, more than 45%, more than 50%, more than 55%, more than 60%, more than 65%, or more than 70% by weight based on the total weight of the electrode slurry.
[0202] There is no particular restriction on the method used when producing the electrode slurry from each electrode component, but all electrode components should be mixed (e.g., by mixing in a homogenizer) to form a homogenized electrode slurry. In some embodiments, all materials used to produce the electrode slurry are added to the homogenizer at one time. In other embodiments, each electrode component of the electrode slurry can be added to the homogenizer in one or more batches, and each batch can contain more than one electrode component. Any homogenizer that can reduce or eliminate particle aggregation and / or promote uniform distribution of electrode components in the electrode slurry can be used in the present invention. Uniform distribution plays an important role in preparing batteries with good battery performance. In some embodiments, the homogenizer is a planetary stirring mixer, a stirring mixer, a mixer or an ultrasonic generator.
[0203] There are no particular restrictions on the conditions used to form the electrode slurry, but these conditions should be sufficient to produce a homogenous slurry with good dispersion of the electrode components in the slurry. There are no particular restrictions on the time, temperature or stirring speed used when homogenizing the electrode slurry, but the time, temperature and stirring speed should be sufficient to ensure that the electrode components in the electrode slurry are evenly distributed and the electrode slurry is easy to process.
[0204] In some embodiments, after homogenizing the electrode slurry, the electrode slurry can be applied to one or both sides of the modified current collector of the present invention to form an electrode layer. There are no particular restrictions on the equipment and conditions used for slurry coating, but the electrode layer film formed should be uniform, flat and smooth. In certain embodiments, the coating process is carried out using a blade coater, a slit extrusion coater, a transfer coater, a spray coater, a roll coater, a gravure coater, a dip coater or a curtain coater. In some embodiments, the electrode slurry is directly applied to the modified current collector. In other embodiments, the electrode slurry is first applied to a release film to form an independent electrode layer. Then, the independent electrode layer is combined with the modified current collector and pressed to form an electrode layer.
[0205] In some embodiments, after the electrode slurry is applied to the modified current collector of the present invention, the coating is dried. Any device that can dry the coating to fix the electrode layer to the modified current collector can be used in the present invention.
[0206] There is no particular limitation on the conditions used during drying, but the drying conditions should be sufficient to ensure that the electrode layer is firmly adhered to the modified current collector. However, drying the electrode slurry at a temperature above 100° C. may cause undesirable deformation of the electrode, thereby affecting the performance of the resulting electrode. In some embodiments, the resulting electrode is mechanically compressed after the film is dried to increase the density of the electrode.
[0207] In certain embodiments, the thickness of the electrode layer is from about 5 μm to about 90 μm, from about 5 μm to about 50 μm, from about 5 μm to about 25 μm, from about 10 μm to about 90 μm, from about 10 μm to about 50 μm, from about 10 μm to about 30 μm, from about 15 μm to about 90 μm, from about 20 μm to about 90 μm, from about 25 μm to about 90 μm, from about 25 μm to about 80 μm, from about 25 μm to about 70 μm, from about 25 μm to about 50 μm, from about 30 μm to about 90 μm, or from about 30 μm to about 80 μm. In some embodiments, the thickness of the electrode layer is greater than 5 μm, greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 25 μm, greater than 30 μm, greater than 40 μm, greater than 50 μm, greater than 60 μm, greater than 70 μm, or greater than 80 μm. In some embodiments, the thickness of the electrode layer is less than 90 μm, less than 80 μm, less than 70 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, less than 25 μm, less than 20 μm, less than 15 μm, or less than 10 μm.
[0208] In some embodiments, the surface density of the electrode layer is about 1 mg / cm 2 To about 50mg / cm 2 , about 2.5mg / cm 2 To about 50mg / cm 2 , about 5mg / cm 2 To about 50mg / cm 2 , about 10mg / cm 2 To about 50mg / cm 2 , about 15mg / cm 2 To about 50mg / cm 2 , about 20mg / cm 2 To about 50mg / cm 2 , about 30mg / cm 2 To about 50mg / cm 2 , about 1mg / cm 2 To about 30mg / cm 2 , about 2.5mg / cm 2 To about 30mg / cm 2 , about 5mg / cm 2 To about 30mg / cm 2, about 10mg / cm 2 To about 30mg / cm 2 , about 15mg / cm 2 To about 30mg / cm 2 , about 20mg / cm 2 To about 30mg / cm 2 , about 1mg / cm 2 To about 20mg / cm 2 , about 2.5mg / cm 2 To about 20mg / cm 2 , about 5mg / cm 2 To about 20mg / cm 2 , about 10mg / cm 2 To about 20mg / cm 2 , about 1mg / cm 2 To about 15mg / cm 2 , about 2.5mg / cm 2 To about 15mg / cm 2 , about 5mg / cm 2 To about 15mg / cm 2 or about 10 mg / cm 2 To about 15mg / cm 2 .
[0209] In some embodiments, the surface density of the electrode layer is less than 50 mg / cm 2 Less than 40mg / cm 2 Less than 30mg / cm 2 Less than 20mg / cm 2 Less than 15mg / cm 2 Less than 10mg / cm 2 Less than 5mg / cm 2 or less than 2.5 mg / cm 2 In some embodiments, the surface density of the electrode layer is greater than 1 mg / cm 2 , greater than 2.5mg / cm 2 , greater than 5mg / cm 2 , greater than 10mg / cm 2 , greater than 15mg / cm 2 , greater than 20mg / cm 2 , greater than 30mg / cm 2 or greater than 40 mg / cm 2 .
[0210] In the electrode comprising the modified current collector of the present invention, the electrode layer exhibits strong adhesion to the modified current collector. It is important that the electrode layer has high peel strength to the modified current collector because this prevents the peeling or separation of the electrode, which will greatly affect the mechanical stability of the electrode and the cyclability of the battery comprising the electrode. Therefore, the electrode should have sufficient peel strength to withstand the rigors of the battery manufacturing process.
[0211] In some embodiments, the peel strength between the electrode layer and the modified current collector ranges from about 1.0 N / cm to about 8.0 N / cm, about 1.0 N / cm to about 6.0 N / cm, about 1.0 N / cm to about 5.0 N / cm, about 1.0 N / cm to about 4.0 N / cm, about 1.0 N / cm to about 3.0 N / cm, about 1.0 N / cm to about 2.0 N / cm, about 2.0 N / cm to about 8.0 N / cm, about 2.0 N / cm to about 6.0 N / cm, about 2.0 N / cm to about 5.0 N / cm, about 2.0 N / cm to about 3.0 N / cm, about 3.0 N / cm to about 8.0 N / cm, about 3.0 N / cm to about 6.0 N / cm, or about 4.0 N / cm to about 6.0 N / cm.
[0212] In some embodiments, the peel strength between the electrode layer and the modified current collector is greater than 1.0 N / cm, greater than 1.5 N / cm, greater than 2.0 N / cm, greater than 2.5 N / cm, greater than 3.0 N / cm, greater than 3.5 N / cm, greater than 4.0 N / cm, greater than 4.5 N / cm, greater than 5.0 N / cm, greater than 5.5 N / cm, greater than 6.0 N / cm, greater than 6.5 N / cm, or greater than 7.0 N / cm. In some embodiments, the peel strength between the electrode layer and the modified current collector is less than 8.0 N / cm, less than 7.5 N / cm, less than 7.0 N / cm, less than 6.5 N / cm, less than 6.0 N / cm, less than 5.5 N / cm, less than 5.0 N / cm, less than 4.5 N / cm, less than 4.0 N / cm, less than 3.5 N / cm, less than 3.0 N / cm, less than 2.5 N / cm, less than 2.0 N / cm, or less than 1.5 N / cm.
[0213] In some embodiments, once an electrode including a modified current collector is formed, the electrode can be assembled with an electrode of opposite polarity and an electrolyte to form a battery.
[0214] In some embodiments, the electrolyte is a liquid electrolyte. This liquid electrolyte comprises an electrolyte solvent and a salt. In some embodiments, the electrolyte solvent is water; the liquid electrolyte is an aqueous electrolyte. In other embodiments, the electrolyte solvent is a liquid composed of one or more organic solvents; the liquid electrolyte is a non-aqueous electrolyte. In some embodiments, each organic solvent is selected from carbonate-based, ester-based, ether-based or other aprotic solvents. Some non-limiting examples of carbonate-based solvents include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, methylethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate and combinations thereof. Some non-limiting examples of ester-based solvents include methyl acetate, methyl propionate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate and combinations thereof. Some non-limiting examples of ether-based solvents include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran and combinations thereof. Some non-limiting examples of other aprotic solvents include methyl bromide, ethyl bromide, methyl formate, acetonitrile, dimethyl sulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, and combinations thereof.
[0215] In some embodiments, the liquid electrolyte is used in a conventional lithium ion battery. The salt in the liquid electrolyte is a lithium salt. In some embodiments, the lithium salt present in the liquid electrolyte for a conventional lithium ion battery is selected from the group consisting of LiPF6, LiBO2, LiBF4, LiSbF6, LiAsF6, LiAlCl4, LiClO4, LiCl, LiI, LiNO3, LiB(C2O4)2, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2CF2CF3)2, LiC2H3O2, and combinations thereof.
[0216] In some embodiments, the liquid electrolyte is used in a conventional sodium ion battery. The salt in the liquid electrolyte is a sodium salt. In some embodiments, the sodium salt present in the liquid electrolyte for a conventional sodium ion battery is a sodium analog of the above-mentioned lithium salts, wherein the lithium is replaced by sodium. The sodium salts include NaPF6, NaBF4, NaN(SO2CF3)2, NaN(SO2F)2, NaClO4, NaSO3CF3 and combinations thereof. In some embodiments, the salt present in the liquid electrolyte for a conventional sodium ion battery is one or more NaMF x ; wherein each x is 4 or 6; and wherein each M is selected from Al 3+ , B 3+ , Ga 3+ 、In 3+ Sc 3+ , Y 3+ ,La 3+ , P5+ 、As 5+ and their combinations.
[0217] In some embodiments, the electrolyte is a solid electrolyte. In some embodiments, the solid electrolyte is a polymer electrolyte. This polymer electrolyte comprises an ion-conducting polymer and a salt. In some embodiments, the ion-conducting polymer is selected from the group consisting of polyether, polycarbonate, polyacrylate, polysilicon ether, polyphosphazene, polyethylene derivatives, alkylene oxide derivatives, phosphate polymers, polylysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing one or more ion-dissociable groups, copolymers thereof, and combinations thereof. In some embodiments, the ion-conducting polymer is selected from the group consisting of polyacrylonitrile (PAN), polyvinyl carbonate (PEC), polyacrylamide (PAM), polyethylene glycol (PEG), polyethylene oxide (PEO), polyhydroxyethyl methacrylate (P(HEMA)), polyphosphonate (PPh), polysilicon ether, polyamide (PA), polydilactone, polydiester, polyphosphazene (PPHOS), polyurethane (PU), copolymers thereof, and combinations thereof.
[0218] In some embodiments, the polymer electrolyte is used in a solid-state lithium ion battery. In certain embodiments, the salt present in the polymer electrolyte for a solid-state lithium ion battery is one or more of the above-mentioned lithium salts. Similarly, in some embodiments, the polymer electrolyte is used in a solid-state sodium ion battery. In certain embodiments, the salt present in the polymer electrolyte for a solid-state sodium ion battery is one or more of the above-mentioned sodium salts.
[0219] In some embodiments, the solid electrolyte is an inorganic solid electrolyte. In certain embodiments, the inorganic solid electrolyte is used in a solid-state lithium-ion battery. In some embodiments, the inorganic solid electrolyte used in a solid-state lithium-ion battery is selected from sulfides, such as Li2S-P2S5; Li 4-x Ge 1-x P x S4 (LGPS, x is 0.1 to 2); Li 10±1 MP2X 12 (M=Ge, Si, Sn, Al; X=S, Se); Li 3.833 Sn 0.833 As 0.166 S4; Li4SnS4; B2S3-Li2S; 10 SnP2S 12; Li6PS5X argyrodite (where X is a halogen); sulfide LISICON compounds, such as Li 3.25 Ge 0.25 P 0.75 S4; antiperovskites, such as Li3SX (X is Cl or Br); lithium-phosphorus-iodine-oxysulfide; lithium-phosphorus-oxysulfide; lithium-zinc-germanium sulfide; lithium-germanium-sulfide; LLTO-based compounds, such as (La, Li)TiO3; Li6La2CaTa6O 12 ;Li6La2ANb2O 12 (A is Ca and / or Sr); Li2Nd3TeSbO 12 ;Li3BO 2.5 N 0.5 ;Li9SiAlO8; LAGP compound (Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1, 0≤y≤1); Li2O-LATP compounds, such as Al2O3-TiO2-P2O5; Li 1+x Al x Ti 2-x (PO4)3 (where 0≤x≤1, 0≤y≤1); Li 1+x Ti 2- x Al x Si y (PO4) 3-y (where 0≤x≤1, 0≤y≤1); LiAl x Zr 2-x (PO4)3 (where 0≤x≤1, 0≤y≤1); LiTi x Zr 2-x (PO4)3 (where 0≤x≤1, 0≤y≤1); LISICON solid electrolyte; LIPON compound (Li 3+y PO 4- x N x , where 0≤x≤1, 0≤y≤1); perovskite compounds ((La, Li)TiO3); NASICON compounds, such as LiTi2(PO4)3; antiperovskites, such as Li3OX (X is Cl or Br); lithium-aluminum-titanium-silicon phosphates (LATSP); lithium-aluminum oxides; lithium-vanadium-germanium oxides; lithium-zinc-germanium oxides; lithium-filled garnets, such as lithium-californium-zirconium oxides; lithium-californium-zirconium-aluminum oxides; lithium-californium-zirconium-tantalum oxides; Li3N; lithium-aluminum chlorides; and a group consisting of combinations thereof.
[0220] In certain embodiments, the inorganic solid electrolyte is used in a solid-state sodium ion battery. In some embodiments, the inorganic solid electrolyte for a solid-state sodium ion battery is a sodium analog of an inorganic solid electrolyte suitable for the above-mentioned solid-state lithium ion battery, wherein lithium is replaced by sodium. In some embodiments, the inorganic solid electrolyte for a solid-state sodium ion battery is a NASICON-type inorganic solid electrolyte, a sulfur- and phosphorus-containing NaPS sulfide (e.g., 75Na2S-25P2S5), sodium polyaluminate, and a combination thereof.
[0221] In some embodiments, the solid electrolyte is a gel electrolyte. Such a gel electrolyte includes a polymer electrolyte and an electrolyte solvent.
[0222] Due to the presence of a conductive layer in the modified current collector of the present invention, a battery comprising an electrode using the modified current collector exhibits excellent electrochemical properties. Compared with conventional current collectors, the modified current collector of the present invention brings considerable improvements to the electrode, which is achieved by the respective contributions of each component present in the conductive layer of the modified current collector. Specifically, the conductive material reduces the interfacial resistance between the modified current collector and the electrode layer, thereby reducing the inherent capacity loss caused by the internal resistance of the electrode in the battery. The conductive layer also serves as a physical barrier to prevent corrosion of the substrate. The binder material not only provides more effective adhesion between the conductive material particles and between the conductive material particles and the substrate, but also improves the mechanical strength of the electrode as a whole. In addition, even if the aqueous electrode slurry is applied to the conductive layer, the binder material in the conductive layer still maintains excellent adhesion properties, preventing the conductive layer from breaking or peeling off from the substrate.
[0223] The following examples are provided to illustrate the embodiments of the invention, but are not intended to limit the invention to the specific embodiments listed. Unless otherwise indicated, all parts and percentages are by weight. All numerical values are approximate. When a numerical range is given, it should be understood that the embodiments outside the stated range still fall within the scope of the present invention. The specific details described in each embodiment should not be understood as essential features of the present invention.
[0224] Although the present invention has been described in conjunction with a limited number of embodiments, the specific features of one embodiment should not limit other embodiments of the present invention. In some embodiments, the method may include multiple steps not mentioned in the present invention. In other embodiments, the method does not include or substantially does not contain any steps not listed in the present invention. There are variations and changes based on the described embodiments. The attached claims are intended to cover all these changes and modifications that fall within the scope of the present invention. Example
[0225] The interfacial resistance of the cathode was measured by an electrode resistance measurement system (RM2610, HIOKI). Example 1 A) Preparation of Conductive Material Mixture
[0226] 150 g of graphite powder (obtained from Timcal Ltd, Bodio, Switzerland) was added to 500 g of ethanol. After the addition, the mixture was stirred at 1000 rpm at 25° C. for about 75 minutes to form a conductive material mixture. B) Preparation of binder material solution
[0227] The binder material is prepared by the following method. Partially substituted polyvinyl alcohol (PVA; the substituents and their number are based on the desired chemical structure and molar ratio of the structural unit (c) in the final copolymer) and deionized water are added to a flask and heated to 100°C to prepare a 5wt.% PVA solution. Then, an aqueous solution of sodium dodecylbenzene sulfonate is prepared and added to the PVA solution. After stirring at 100°C for 30 minutes, the mixture is cooled to 65°C, and an appropriate weight of n-butanol (based on the desired molar ratio of the structural unit (b) in the final copolymer) is added to the mixture and stirred at 65°C for 30 minutes. The mixture is cooled to below 20°C, and dilute hydrochloric acid is added dropwise to the mixture for more than 25 minutes. Then, the mixture is filtered, washed and dried to obtain a binder material. In the structural unit (a) of the copolymer, any three of R1, R2, R3 and R4 are H; and any one of R1, R2, R3 and R4 is a hydroxyl group. In the structural unit (b) of the copolymer, R5, R6, R7, R8, R9 and R 10 is H; and R 11 In the structural unit (c) of the copolymer, R 12 , R 13 , R 14 and R 15 Any three of them are H; and R 12 , R 13 , R 14 and R 15 Any one of them is an acetoxy group. Based on the total molar number of monomer units in the copolymer, the proportions of structural unit (a), structural unit (b) and structural unit (c) in the copolymer of the binder material are 11.5%, 88% and 0.5% by mole, respectively. The components of the binder material of Example 1 and their respective proportions are shown in Table 1 below.
[0228] Then, 75g of binder material was added to 750g of ethanol. The mixture was stirred at 600rpm for 30 minutes using a magnetic stirrer to form a binder material solution. The solid content of the binder material solution was 9.1% by weight. The weight average molecular weight of the copolymer was 50,000g / mol. C) Preparation of conductive paste
[0229] 150 g of the binder material solution was added to 50 g of the conductive material mixture. After the addition, the mixture was stirred at 25° C. at a speed of 1000 rpm for about 15 minutes to form a conductive paste. The solid content of the conductive paste was 12.6% by weight. D) Preparation of modified current collector
[0230] Aluminum foil with a thickness of 16 μm was used as a substrate. The conductive paste was applied to both sides of the substrate using a knife coater with a gap width of 8 μm. A conductive layer was formed by drying 4.5 μm of the applied paste on the aluminum foil in an electrically heated oven at 85°C. The drying time was about 30 minutes. E) Preparation of binder solution
[0231] 16 g of sodium hydroxide (NaOH) was added to a round bottom flask containing 380 g of distilled water. The sodium hydroxide solution was stirred at 80 rpm for 30 minutes to obtain a first suspension.
[0232] 36.04 g of acrylic acid was added to the first suspension. The mixture was further stirred at 80 rpm for 30 minutes to obtain a second suspension.
[0233] 19.04 g of acrylamide (AM) was dissolved in 10 g of deionized water to form an AM solution. Thereafter, 29.04 g of the AM solution was added to the second suspension. The mixture was further heated to 55° C. and stirred at 80 rpm for 45 minutes to obtain a third suspension.
[0234] 12.92 g of acrylonitrile (AN) was added to the third suspension. The mixture was further stirred at 80 rpm for 10 minutes to obtain a fourth suspension.
[0235] After that, 0.015 g of a water-soluble free radical initiator (ammonium persulfate, APS; obtained from Aladdin Industries, China) was dissolved in 3 g of DI water and 0.0075 g of a reducing agent (sodium bisulfite; obtained from Tianjin Da Mao Chemical Reagent Factory, China) was dissolved in 1.5 g of deionized water. 3.015 g of the APS solution and 1.5075 g of the sodium bisulfite solution were added to the fourth suspension. The mixture was stirred at 200 rpm at 55° C. for 24 hours to obtain a fifth suspension.
[0236] After the reaction is complete, the temperature of the fifth suspension is reduced to 25°C. 3.72g of NaOH is dissolved in 400g of deionized water. Thereafter, 403.72g of sodium hydroxide solution is added dropwise to the fifth suspension to adjust the pH to 7.31 to form a sixth suspension. The binder is filtered using a 200μm nylon mesh. The solid content of the binder solution is 9.00wt.%. F) Preparation of positive electrode
[0237] A first mixture was prepared by dispersing 12 g of a conductive agent (SuperP; obtained from Timcal Ltd, Bodio, Switzerland) and 100 g of a binder solution (9.00 wt.% solids) in 74 g of deionized water while stirring with an overhead stirrer (R20, IKA). After addition, the first mixture was further stirred at 25° C. at a speed of 1,200 rpm for about 30 minutes.
[0238] Thereafter, 276 g of NMC811 (obtained from Shandong Tianjiao New Energy Co., Ltd., China) was added to the first mixture at 25° C. while stirring with an overhead stirrer to prepare a second mixture. The second mixture was then degassed at a pressure of about 10 kPa for 1 hour. The second mixture was further stirred at 25° C. at a speed of 1,200 rpm for about 60 minutes to form a homogenized cathode slurry.
[0239] The homogenized cathode slurry was coated on both sides of the modified current collector prepared above using a knife coater with a gap width of 120 μm. The cathode layer was formed by drying the coated slurry of 80 μm on the modified current collector in an electrically heated oven at 70°C. The drying time was about 10 minutes. The electrode was then pressed to reduce the thickness of the cathode layer to 23 μm. The surface density of the cathode layer on the modified current collector was 7.00 mg / cm 2 The interfacial resistance of the cathode of Example 1 was measured and is shown in Table 1 below. G) Assembly of button cell batteries
[0240] The cathode prepared above was tested for electrochemical performance in a CR2032 button-type Li battery assembled in a glove box filled with argon. The cathode was cut into a disc shape for assembling a button-type battery. A lithium metal foil with a thickness of 500 μm was used as an anode. The cathode and anode were kept separate by a diaphragm. The diaphragm was a ceramic-coated microporous membrane (MPM, Japan) made of non-woven fabric with a thickness of about 25 μm. The electrode assembly was then dried in a box-type resistance furnace (DZF-6020, obtained from Shenzhen Kejing Starlight Technology Co., Ltd., China) at vacuum, 105 ° C for about 16 hours.
[0241] The electrolyte is then injected into the casing containing the packaged electrodes under a high-purity argon environment with a moisture and oxygen content of less than 3 ppm, respectively. The electrolyte is a solution containing LiPF6 (1M) in a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. After the electrolyte is injected, the button cell is mechanically pressed using a punching tool with a standard round shape. H) Electrochemical measurements
[0242] The button cells were analyzed in constant current mode using a multi-channel battery tester (BTS-4008-5V10mA, obtained from China Xinwei Electronics Co., Ltd.). After completing 1 cycle at C / 20, the battery was charged and discharged at a rate of C / 2. The charge / discharge cycle test of the battery was performed at a current density of C / 2, 25°C, between 3.0 and 4.3V to obtain the discharge capacity. The electrochemical properties of the button cells of Example 1 were measured and are shown in Table 1 below. Preparation of Conductive Material Mixtures of Examples 2-8 and 13-15
[0243] Conductive material mixtures of Examples 2-8 and 13-15 were prepared in the same manner as in Example 1. Preparation of the Conductive Material Mixture of Example 9
[0244] A conductive material mixture was prepared in the same manner as in Example 1, except that 150 g of carbon black (obtained from Timcal Ltd, Bodio, Switzerland) was used instead of graphite powder. Preparation of the Conductive Material Mixture of Example 10
[0245] A conductive material mixture was prepared in the same manner as in Example 1, except that 25 g of carbon black was first added to 500 g of ethanol, which was stirred at 1000 rpm for 15 minutes at 25°C to form a mixture; then 125 g of graphite powder was added to the mixture, and further stirred at 1000 rpm for 60 minutes at 25°C to form a conductive material mixture. Preparation of the Conductive Material Mixture of Example 11
[0246] A conductive material mixture was prepared in the same manner as in Example 1, except that 25 g of vapor grown carbon nanofibers (VGCFs; obtained from Showa Denko KK, Japan) were first added to 500 g of ethanol, which was stirred at 1000 rpm for 15 minutes at 25°C to form a mixture; then 125 g of graphite powder was added to the mixture, and further stirred at 1000 rpm for 60 minutes at 25°C to form a conductive material mixture. Preparation of the Conductive Material Mixture of Example 12
[0247] A conductive material mixture was prepared in the same manner as in Example 1, except that 25 g of carbon nanotubes (CNTs; obtained from Jiangsu Tiannai Technology Co., Ltd., China) were first added to 500 g of ethanol, which was stirred at 1000 rpm for 15 minutes at 25°C to form a mixture; then 125 g of graphite powder was added to the mixture, and further stirred at 1000 rpm for 60 minutes at 25°C to form a conductive material mixture. Preparation of Binder Material Solution of Example 2
[0248] A binder material solution was prepared in the same manner as in Example 1, except that the weight average molecular weight of the copolymer was 120,000 g / mol. Preparation of Binder Material Solution of Example 3
[0249] The binder material solution was prepared in the same manner as in Example 1, except that the proportions of structural unit (a) and structural unit (b) in the copolymer of the binder material were 19.5% and 80% by mole, respectively, based on the total molar number of monomer units in the copolymer, and the weight average molecular weight of the copolymer was 170,000 g / mol. Preparation of Binder Material Solution of Example 4
[0250] A binder material solution was prepared in the same manner as in Example 3, except that the weight average molecular weight of the copolymer was 200,000 g / mol. Preparation of Binder Material Solution of Example 5
[0251] A binder material solution was prepared in the same manner as in Example 3, except that the weight average molecular weight of the copolymer was 250,000 g / mol. Preparation of Binder Material Solution of Example 6
[0252] A binder material solution was prepared in the same manner as in Example 1, except that the proportions of structural unit (a), structural unit (b) and structural unit (c) in the copolymer of the binder material were 18.5%, 80% and 1.5% by mole, respectively, based on the total molar number of monomer units in the copolymer, and the weight average molecular weight of the copolymer was 170,000 g / mol. Preparation of Binder Material Solution of Example 7
[0253] A binder material solution was prepared in the same manner as in Example 1, except that the proportions of structural unit (a), structural unit (b) and structural unit (c) in the copolymer of the binder material were 17.5%, 80% and 2.5% by mole, respectively, based on the total molar number of monomer units in the copolymer, and the weight average molecular weight of the copolymer was 250,000 g / mol. Preparation of Binder Material Solution of Example 8
[0254] The binder material solution was prepared in the same manner as in Example 1, except that the proportions of the structural unit (a) and the structural unit (b) in the copolymer of the binder material were 20% and 80% by mole, respectively, based on the total moles of the monomer units in the copolymer, and the copolymer did not contain the structural unit (c). The weight average molecular weight of the copolymer was 170,000 g / mol. Preparation of Binder Material Solutions of Examples 9-15
[0255] In the same manner as in Example 4, binder material solutions of Examples 9 to 15 were prepared. Preparation of Conductive Paste of Examples 2-15
[0256] Conductive pastes of Examples 2 to 15 were prepared in the same manner as in Example 1. Preparation of the modified current collector of Example 2-15
[0257] The modified current collectors of Examples 2 to 15 were prepared in the same manner as in Example 1. Preparation of Binder Solutions of Examples 2-15
[0258] The binder solutions of Examples 2-15 were prepared in the same manner as in Example 1. Preparation of the positive electrode of Example 2-12
[0259] The positive electrodes of Examples 2 to 12 were prepared in the same manner as in Example 1. Preparation of the positive electrode of Example 13
[0260] The positive electrode was prepared in the same manner as in Example 1, except that the same weight of LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA, obtained from Shandong Tianjiao New Energy Co., Ltd., China) replaced 276 g of NMC811. Preparation of the positive electrode of Example 14
[0261] The positive electrode was prepared in the same manner as in Example 1, except that the same weight of NMC532 as the core and Li 0.95Ni 0.53 Mn 0.29 Co 0.15 Al 0.03 The core-shell cathode active material (CS) with O2 as the shell replaced 276g of NMC811. Preparation of the positive electrode of Example 15
[0262] The positive electrode was prepared in the same manner as in Example 1, except that the same weight of LiFePO4 (LFP, obtained from Shenzhen Defang Nanotechnology Co., Ltd., China) was used instead of 276 g of NMC811 in the preparation of the positive electrode. Assembly of the button cell of Example 2-15
[0263] The button cells of Examples 2 to 15 were assembled in the same manner as in Example 1. Electrochemical measurements of Examples 2-14
[0264] The electrochemical properties of the button cells of Examples 2 to 14 were measured in the same manner as in Example 1, and the test results are shown in Table 1 below. Electrochemical Measurements of Example 15
[0265] The electrochemical properties of the button cell of Example 15 were measured in the same manner as in Example 1, except that the charge / discharge cycle test of the cell was conducted at a current density of C / 2, at 25° C., between 2.00 and 3.65 V to obtain the discharge capacity. The test results are shown in Table 1 below. Comparative Example 1
[0266] A button cell was prepared in the same manner as in Example 1. The difference was that a conventional current collector was used (i.e., no conductive slurry was prepared, and the cathode slurry was directly coated on an aluminum foil). The electrochemical properties of the button cell of Comparative Example 1 were measured in the same manner as in Example 1. Comparative Examples 2-4
[0267] A button cell was prepared using the same method as in Example 1, except for the following changes. Preparation of Conductive Material Mixture of Comparative Examples 2-4
[0268] The conductive material mixtures of Comparative Examples 2-4 were prepared using the same method as in Example 1. Preparation of Binder Material Solution of Comparative Example 2
[0269] A binder material solution was prepared in the same manner as in Example 3, except that the weight average molecular weight of the copolymer was 40,000 g / mol. Preparation of Binder Material Solution of Comparative Example 3
[0270] A binder material solution was prepared in the same manner as in Example 1, except that based on the total molar number of monomer units in the copolymer, the proportions of structural unit (a), structural unit (b) and structural unit (c) in the copolymer of the binder material were 23%, 75% and 2%, respectively, and the weight average molecular weight of the copolymer was 150,000 g / mol. Preparation of Conductive Paste of Comparative Example 2-3
[0271] The conductive paste of Comparative Example 2-3 was prepared in the same manner as in Example 1. Preparation of the modified current collector of Comparative Example 2-3
[0272] The modified current collector of Comparative Example 2-3 was prepared in the same manner as in Example 1. Binder of Comparative Example 2-3 Solution preparation
[0273] The binder solution of Comparative Example 2-3 was prepared in the same manner as in Example 1. Preparation of the positive electrode of Comparative Example 2-3
[0274] The positive electrode of Comparative Example 2-3 was prepared in the same manner as in Example 1. Assembly of button cell of Comparative Example 2-3
[0275] The button cells of Comparative Examples 2-3 were assembled using the same method as in Example 1. Electrochemical measurements of Comparative Examples 2-3
[0276] The electrochemical properties of the button cells of Comparative Examples 2-3 were measured in the same manner as in Example 1, and the test results are shown in Table 1 below. Comparative Example 4
[0277] The button cell was prepared using the same method as in Example 15, except that a conventional current collector was used (i.e., no conductive slurry was prepared, and the cathode slurry was directly coated on the aluminum foil). The electrochemical properties of the button cell of Comparative Example 4 were measured using the same method as in Example 15.
[0278] Although the present invention has been described in conjunction with a limited number of embodiments, the specific features of one embodiment should not limit other embodiments of the present invention. In some embodiments, the method may include multiple steps not mentioned in the present invention. In other embodiments, the method does not include or substantially does not contain any steps not listed in the present invention. There are variations and changes based on the described embodiments. The attached claims are intended to cover all these changes and modifications that fall within the scope of the present invention.
Claims
1. A modified current collector for a secondary battery, comprising a substrate and a conductive layer applied on one or both sides of the substrate, wherein the conductive layer comprises a conductive material and a binder material, wherein the binder material comprises a copolymer containing a structural unit (a), wherein the structural unit (a) comprises one or more monomer units having formula (1): And wherein R1, R2, R3 and R4 in formula (1) are each independently H, hydroxyl, alkyl, hydroxyalkyl, halogen or halogenated alkyl.
2. The modified current collector according to claim 1, wherein the copolymer further comprises a structural unit (b), wherein the structural unit (b) comprises one or more monomer units having formula (2): And wherein R5, R6, R7, R8, R9, R 10 and R 11 Each is independently H, alkyl, halogen or haloalkyl.
3. The modified current collector according to claim 2, wherein the copolymer further comprises a structural unit (c), wherein the structural unit (c) comprises one or more monomer units having formula (3): And R in formula (2) 12 , R 13 , R 14 and R 15 Each is independently H, alkyl, acyloxy, acyloxyalkyl, halogen or haloalkyl.
4. The modified current collector according to claim 1, wherein the proportion of the structural unit (a) in the copolymer is about 5 to about 20% by mole based on the total moles of the monomer units in the copolymer.
5. The modified current collector according to claim 2, wherein the proportion of the structural unit (b) in the copolymer is about 80% to about 90% by mole based on the total moles of the monomer units in the copolymer.
6. The modified current collector according to claim 3, wherein the proportion of the structural unit (c) in the copolymer is about 0% to about 5% by mole based on the total moles of the monomer units in the copolymer. 7 . The modified current collector according to claim 2 , wherein a molar ratio of the structural unit (b) to the structural unit (a) in the copolymer is from about 4 to about 15. 8 . The modified current collector according to claim 1 , wherein the thickness of the modified current collector is about 5 μm to about 70 μm.
9. The modified current collector according to claim 1, wherein the substrate is selected from the group consisting of stainless steel, titanium, nickel, aluminum, copper, platinum, gold, silver, chromium, zirconium, tungsten, molybdenum, silicon, tin, vanadium, zinc, cadmium, alloys thereof, conductive resins, and combinations thereof.
10. The modified current collector according to claim 1, wherein the conductive material is selected from the group consisting of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon tubes, carbon nanotubes, activated carbon, Super P, KS6, vapor grown carbon fibers (VGCF), mesoporous carbon, and combinations thereof. 11 . The modified current collector according to claim 3 , wherein the copolymer has a weight average molecular weight of about 50,000 g / mol to about 300,000 g / mol. 12 . The modified current collector according to claim 1 , wherein the conductive material accounts for about 20% to about 80% by weight in the conductive layer based on the total weight of the conductive layer. 13 . The modified current collector according to claim 1 , wherein the binder material accounts for about 20% to about 80% by weight in the conductive layer based on the total weight of the conductive layer. 14 . The modified current collector according to claim 1 , wherein the hydroxyalkyl group is selected from the group consisting of a hydroxymethyl group, a hydroxyethyl group, a hydroxypropyl group, a hydroxy(methyl)propyl group, a hydroxy(methyl)butyl group, and a combination thereof. 15 . The modified current collector according to claim 3 , wherein the acyloxyalkyl group is selected from the group consisting of an acyloxymethyl group, an acyloxyethyl group, an acyloxypropyl group, an acyloxy(methyl)propyl group, an acyloxy(methyl)butyl group, and a combination thereof. 16 . An electrode comprising the modified current collector of claim 1 and an electrode layer, wherein the electrode layer is located on a surface of a conductive layer, and wherein the electrode layer comprises an electrode active material and a binder.
17. The electrode according to claim 16, wherein the electrode active material is selected from LiCoO2, LiNiO2, LiNi 1-x M x O2、LiNi x Mn y O2、LiCo x Ni y O2、Li 1+z Ni x Mn y Co 1-x-y O2、LiNi x Co y Al z A cathode active material selected from the group consisting of LiO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4 and combinations thereof; wherein each x is independently 0.1 to 0.9; each y is independently 0 to 0.9; each z is independently 0 to 0.4; and wherein M is selected from the group consisting of Co, Mn, Al, Fe, Ti, Ga, Mg and combinations thereof.
18. The electrode according to claim 16, wherein the electrode active material is a cathode active material selected from the group consisting of NaCoO2, NaFeO2, NaNiO2, NaCrO2, NaVO2, NaTiO2, NaFePO4, Na3V2(PO4)3, Na3V2(PO4)2F3, NMC-based mixed oxides, Prussian blue-based sodium compounds, and combinations thereof.
19. The electrode according to claim 16, wherein the electrode active material is selected from natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particles, SnO2, SnO, Li4Ti2O 12 An anode active material comprising a group consisting of particles, Si particles, Si-C composite particles and combinations thereof.
20. An electrode according to claim 16, wherein the binder comprises a polymer, wherein the polymer comprises one or more functional groups containing halogen, O, N, S or a combination thereof; and wherein the functional groups are each independently selected from the group consisting of carboxylic acid, carboxylate, sulfonic acid, sulfonate, sulfuric acid, sulfate, phosphonic acid, phosphonate, phosphoric acid, phosphate, nitric acid, nitrate, amide, hydroxyl, nitrile, ester, epoxy, -NH2 and a combination thereof.
Citation Information
Patent Citations
Current collector
US20130295458A1